Mulheres lutando contra o HIV/SIDA: cuidadoras de Moçambique - Casimiro, Isabel Maria; Fauré, Yves-A; Tembe, Carlota Mondlane; Mutisse, Luisa Chicamisse (Desafios para Moçambique 2022, 2022)
Moçambique é um país caracterizado por índices elevados de pobreza onde a prevalência do Vírus da Imunodeficiência Humana (HIV)/Síndrome da Imunodeficiência Adquirida (SIDA) é muito alta e a taxa de incidência ainda preocupante, e cujos meios de combate à doença são limitados e dependem, em parte, da ajuda externa. A súbita emergência e rápida expansão da covid-19, a partir do início de 2020, teve um impacto negativo nas condições de tratamento das PVHIV, que, de certa forma, sofreram uma dupla aflição. Os serviços de saúde essenciais foram afectados - prevenção, diagnóstico, tratamento, cuidados paliativos e reabilitativos, etc. - com efeitos graves nos doentes mais vulneráveis (crianças, idosos, pessoas que vivem com doenças crónicas). Com este estudo, pretendemos apresentar os resultados obtidos através da divulgação das iniciativas das mulheres junto às autoridades públicas, instituições nacionais e internacionais, agências de cooperação bilaterais, associações e ONGs moçambicanas e estrangeiras dedicadas de uma ou de outra forma à luta contra o HIV/SIDA. Finalmente, almejamos examinar as condições em que estas iniciativas poderiam ser integradas ou pelo menos aproximadas das Unidades Sanitárias que trabalham na área do HIV/SIDA.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; gender / género; health / saúde; society / sociedade

A questão do género sob uma perspectiva histórica, nas políticas de saúde em Moçambique - Rosário, Carmeliza (Desafios para Moçambique 2022, 2022)
O presente capítulo é baseado numa revisão histórica das políticas sociais desenvolvidas em Moçambique. Dentre as políticas sociais do País, a saúde tem sido consistentemente um dos sectores privilegiados. Já durante o tempo colonial, apesar das políticas discriminatórias entre a população indígena e a colonial, a saúde sempre figurou como preocupação governativa, particularmente em benefício das populações trabalhadoras assalariadas, em detrimento das não assalariadas. Além disso, os aspectos discriminatórios estendiam-se também à priorização dos homens como força laboral e à visão das mulheres e crianças como dependentes, criando inclusivamente benefícios maiores para homens casados e cimentando a perspectiva do homem como provedor. Na análise que se segue, apresenta-se o percurso legislativo do sector de saúde e os ideais preconizados nesta legislação, com particular atenção para a mulher e a sua consideração na mesma. De seguida, apresenta-se a desconexão estrutural que se tem verificado, em relação aos ideais preconizados. Por fim, apresentam-se exemplos sobre como as políticas de outros sectores podem afectar o sector da saúde e produzir efeitos transformadores incluindo de impacto para a equidade de género. Para tal, argumenta-se que, pese embora os desafios que o País enfrenta, de crises recorrentes, falta de recursos e dependência pela ajuda externa, é necessário determinar o tipo de Estado que se quer, social ou mercantilista. Deve ainda ultrapassar-se a visão limitada da saúde da mulher relacionada com sexualidade e reprodução e do papel do homem na saúde como condutor ou repressor dessas funções da mulher.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; gender / género; society / sociedade

Classes of working women in Mozambique: an integrated framework to understand working lives - Stevano, Sara (Review of International Political Economy, 2022)
Feminist political economy has illuminated the gendered dimensions of the globalisation of production. Whilst this literature provides essential insights on gendered exploitation in export-oriented industries, women’s work in localised labour markets in the Global South remains underexplored. This paper seeks to address this gap by putting into dialogue three bodies of literature – feminist political economy of globalisation, political economy of development in southern Africa and the social reproduction of the everyday. It proposes an integrated conceptual framework to analyse women’s working lives and applies it to northern Mozambique. It makes two key findings. First, the lives of those working in localised labour markets are shaped by global capitalism through extreme fragmentation of labour regimes forcing people into multiple precarious forms of work – a process that entails the appropriation of women’s productive and reproductive labour. Second, the imperatives of social reproduction shape employment trajectories and expose differentiation among working women, seen for example through gendered constraints to mobility, care obligations and contributions to ceremonies. The implications are that the analysis of women’s working lives needs to capture three key aspects: social differentiation among working women, temporal and spatial dynamics of the everyday and the centrality of the reproduction of the social.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; gender / género; labour regimes / regimes de trabalho; social protection / proteção social; social reproduction / reprodução social

The Role of Women in the Conflict in Cabo Delgado: Understanding Vicious Cycles of Violence - Feijó, João (Observatório do Meio Rural, 2021)
Since October 2017, Cabo Delgado Province has been an arena of armed conflict, translating into destruction and looting, abductions and killings of civilian populations. The conflict intensified throughout 2020, with attacks on district headquarters villages, leading to the forced displacement of hundreds of thousands of individuals. The history of armed conflicts in Mozambique shows that they have had enormous impacts on the civilian population, placed between two opposing groups: rebel forces and government forces. Aware of their respective importance in a guerrilla war (for the possibility of logistical support, camouflage, recruitment, or the provision of information), the warring parties have always related to the civilian population on the basis of mistrust, imposing their domination by force and persuasion, and seeking to interfere in their habitat (in clusters or scattered in the bush). Being physically more fragile, target for sexual predation by armed young men, and traditionally a food producer, women were a recurrent target, remaining in a particularly vulnerable position. In the current armed conflict in northeast Cabo Delgado, there have been numerous reports of abduction of hundreds of young women, and there is much doubt about their whereabouts. However, viewing women only as passive victims of the conflict does not capture the complexity of the situation. Voluntarily or forcibly, by conviction or without choice, the literature shows that women play an active role in armed conflicts, as observers and providers of military information, in providing logistical support, as vigilantes, and even as soldiers. This active involvement of women is all the more evident the larger the social support base of the insurgent groups. This study aims to portray the impact of the armed conflict on women during the armed conflict in northern Cabo Delgado, analyzing not only the wide range of violence committed against them, but also the forms of collaboration (more or less voluntary) with rebel groups and their organizational dynamics.
ISBN: 978-2-490093-28-1
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; Northern PEA; conflict / conflito; gender / género; ⛔ No DOI found

Caracterização e Organização Social Dos Machababos a Partir dos Discursos de Mulheres Raptadas - Feijó, João (Observatório do Meio Rural, 2021)
A intensificação do conflito militar no Norte de Cabo Delgado despertou a atenção de jornalistas, investigadores, analistas de segurança e diplomatas. O facto de os rebeldes armados não darem entrevistas a jornalistas e investigadores resulta num grande desconhecimento sobre as suas dinâmicas internas nas zonas ocupadas, pelo que o mundo dos insurgentes constitui um território repleto de mistérios. Por outro lado, o rapto de centenas de jovens mulheres gera interrogações em torno do respectivo paradeiro, originando inquietação social. O pouco conhecimento existente acerca das formas de organização interna dos insurgentes resulta de testemunhos oculares de quem privou com o grupo, nomeadamente desertores ou mulheres que estiveram em cativeiro. A partir de 23 entrevistas a mulheres vítimas de agressão ou sequestro por grupos insurgentes foi possível concluir que os membros do grupo têm origens e percursos sociogeográficos heterogéneos, sendo a maioria oriunda do litoral Norte de Cabo Delgado, com registos de indivíduos provenientes do planalto de Mueda, do litoral de Nampula, assim como um crescente número de estrangeiros, provenientes da costa oriental africana e de países árabes. Os insurgentes dispõem de diferentes bases, instaladas em aldeias abandonadas por civis ou nas matas.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; gender / género

Characterization and Social Organization of Machababos from the Discourses of Kidnapped Women - Feijó, João (Observatório do Meio Rural, 2021)
The intensification of the military conflict in Northern Cabo Delgado has attracted the attention of journalists, investigators, security analysts and diplomats. The fact that armed rebels do not give interviews to journalists and researchers results in a great ignorance about their internal dynamics in the occupied areas, and so the world of insurgents is a territory full of mysteries. On the other hand, the abduction of hundreds of young women raises questions about their whereabouts, causing social unrest. The little knowledge of the insurgents' forms of internal organization stems from eyewitness testimonies of those who lived with the group, including defectors or women who have been in captivity.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; gender / género

Shaping Social Change with Music in Maputo, Mozambique - Taela, Kátia; Gonçalves, Euclides; Maivasse, Catija; Manhiça, Anésio (IDS, 2021)
In Mozambique, development programmes have traditionally drawn on music as a means to promote social transformation by educating citizens on key social development issues. Shifting the focus from music as a teaching medium to music as a rich source of information can provide vital insights into public opinion and political ideas, and significantly impact the development of citizen engagement projects. Maximum gains for development and civil society agencies can be achieved by mainstreaming gender into mutual learning activities between singers, audiences, and academics.
Keywords: *tagged; G - Mozambique / Moçambique; G - south / sul; GP - Maputo; L - english / inglês; M - ethnography / etnografia; accountability / responsabilização; citizenship & participation / cidadania e participação; decentralization / descentralização; empowerment / empoderamento; gender / género

Relatório de Pesquisa Desigualdades e Resistência em Tempos de Pandemia: Impactos Da COVID-19 Nas Mulheres do Mercado Informal - Osório, Conceição; Loforte, Ana Maria; Vilanculo, Sérgio (WLSA Moçambique, 2021)
Este relatório de pesquisa buscou especificamente identificar no contexto mundial, regional e nacional as estratégias e as políticas públicas relativamente à situação das raparigas e mulheres, analisar as narrativas e discursos das organizações da sociedade civil e instituições de pesquisa, tanto as que têm como foco os direitos humanos, como as que definem como objecto a promoção da igualdade de género, e analisar o conteúdo dos media nacionais sobre a Covid-19, com destaque para as representações sobre violência de género. Para a realização da pesquisa foi importante a definição do grupo alvo, as mulheres que trabalham no informal, por serem das mais afectadas pela situação criada pela Covid-19, sendo muito pouco conhecidas as suas vozes, os seus problemas, necessidades e expectativas. A pesquisa foi enquadrada no Projecto “Mulheres e direitos humanos no contexto da COVID-19 em Moçambique” e surgiu no âmbito de uma parceria entre a WLSA Moçambique com as Aliadas e o CESC, procurando conhecer melhor como é que, em situação de pandemia, se configuravam os direitos humanos das mulheres, considerando as desigualdades estruturais e as relações desiguais de poder.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; civil society / sociedade civil; gender / género; health - COVID-19 / saúde – COVID-19; health / saúde; informality / informalidade

Innovative Finance for Employment: The Potential for Women and Urban Youth - MUVA; Social Finance Ltd (MUVA and Social Finance Ltd, 2021)
The need for female economic empowerment in Mozambique is clear; just 24% of women have access to wage employment, versus 50% of men. The situation is worse still in urban settings where 19-24-year-old women have the highest unemployment rates in the country. The national rate of formal employment is approximately 13%, and large scale formal job creation in the Oil and Gas sector is yet to materialise. Despite impressive economic growth in recent years, 50% of Mozambicans are still living in poverty and social and economic inequalities are continuing to grow. The challenges faced by disadvantaged urban youth and women (DUYW) are severe; without deliberate intervention to address the constraints facing them, this trend is set to worsen. In light of this challenge, MUVA commissioned a scoping study to assess the potential of innovative financing models to support the economic empowerment of disadvantaged urban youth and women. Innovative finance is a broad spectrum of mechanisms that offer an alternative to traditional activity based grant funding. It can include investment capital seeking a return, but also encompasses results based financing and broader risk mitigation mechanisms. If done correctly, innovative finance can support good interventions to better tackle entrenched social issues, by sharpening incentives, creating accountability for results, addressing specific barriers in the system, shifting where risk is held and fostering adaptive management. The study identified four innovative financing models that have the potential to enable disadvantaged urban youth and women in Mozambique to access economic opportunities. Some focus more on the supply side, working primarily with DUYW to improve their skills, employability and facilitate entry into the workforce. Others focus on the demand side, working with enterprises to enable them to scale, improve gender practices and encourage them to employ DUYW. Two of the shortlisted models sit across both demand and supply.
Keywords: G - Mozambique / Moçambique; L - english / inglês; employment / emprego; empowerment / empoderamento; gender / género; private sector / setor privado; urbanization / urbanização; youth / juventude

Qualidade da assistência pré-natal em Nampula, Moçambique - Muleva, Belarmina Reis (Universidade de São Paulo, 2020)
A realização da consulta pré-natal de alta qualidade está diretamente relacionada aos melhores indicadores maternos e fetais e à prevenção de morbimortalidade materna. Em Moçambique, estudos sobre assistência pré-natal mostram que a maior parte das mulheres fez pré-natal, mas apenas metade fez as quatro ou mais consultas preconizadas pelo Ministério da Saúde. Além disso, as gestantes têm se apresentado aos centros de saúde para fazerem sua primeira consulta pré-natal somente no final do segundo trimestre da gestação. Essas questões mostram que a qualidade da assistência ao pré-natal é ainda um desafio, embora haja poucos estudos sobre o tema naquele contexto. Objetivo: Avaliar a qualidade da assistência pré-natal entre as mulheres do município de Nampula, em Moçambique. Método: Trata-se de um estudo quantitativo, do tipo transversal, realizado no município de Nampula, em Moçambique, na África. A amostra constou de 393 mulheres de 18 a 49 anos, com parto ocorrido em maternidade ou no domicílio no segundo semestre de 2019. As entrevistas foram conduzidas por meio de instrumento estruturado, aplicado face-a-face, até 15 dias após o parto. A qualidade da assistência pré-natal foi analisada com base nas diretrizes do Ministério da Saúde de Moçambique. A qualidade do pré-natal foi categorizada em inadequada e adequada. Modelos de regressão logística múltipla foram conduzidos para analisar os aspectos associados a ter realizado pré-natal adequado. Resultados: As mulheres participantes do estudo tinham, em média, 26 anos de idade, e metade tinha ensino primário (52,4%). Embora todas as mulheres tenham realizado o pré-natal, apenas 13,0% tiveram o pré-natal classificado como adequado. Mulheres que realizaram pré-natal em gestações anteriores (OR=4,28; IC95%=1,45-12,62) e com gravidez planejada (OR=2,51; IC95%=1,11-5,68) foram as que tiveram mais chance de ter um pré-natal adequado. Observou-se que a assistência pré-natal não atendeu ao que é preconizado, como a idade gestacional de início do pré-natal, número mínimo de consultas a serem feitas, realização de alguns exames (hemograma, glicemia, tipagem sanguínea e fator Rh) e oferta de orientações sobre sinais de risco e de parto. Quanto à satisfação com a assistência pré-natal recebida, mais da metade das mulheres mostrou-se insatisfeita com o tempo de espera para ser atendida pela profissional de saúde. Conclusão: De modo geral, os critérios preconizados para que uma assistência ao pré-natal seja de alta qualidade não estão incorporados na prática clínica no município de Nampula.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; Health PEA; L - portuguese / português; gender / género; health - dignified care / saúde - atendimento humanizado / mau atendimento; health - health services / serviços de saúde; health - maternal and child / saúde - materno-infantil; health / saúde

Gender and countering violent extremism (CVE) in the Kenya- Mozambique region - Idris, Iffat (Institute of Development Studies, 2020)
This evidence synthesis drew on a mixture of academic and grey literature. While the literature on Kenyan women and Al-Shabaab was quite extensive (albeit with gaps, e.g. on returnees), nothing was found on women and Ansar al-Sunnah/violent extremist groups operating in northeastern Mozambique and the Mozambique-Tanzania cross-border region. This report should be read in conjunction with two earlier reviews of gender and CVE (Idris & Abdelaziz, 2017; Idris, 2019). This report builds on those – focusing on the literature on gender and CVE published since then, and on recent guidance on CVE programming – rather than reproducing their findings. This report covers three main themes: the role of women in violent extremism and in CVE (drawing on global evidence); Kenyan women’s involvement in Al-Shabaab and approaches to CVE and gender in that country; and recommendations/guidance for gender and CVE programming.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; gender / género

O Trabalho Doméstico Em Moçambique: Uma Década após a Formalização - Castel-Branco, Carlos Nuno (Desafios para Moçambique 2020, 2020)
O estudo verifica que houve alguns avanços na última década, incluindo: a definição de um quadro regulamentar para o trabalho doméstico, a proliferação de organizações de trabalhadores domésticos filiadas ao movimento sindical e uma maior valorização por parte da sociedade (e dos empregadores) deste sector. No entanto, existem vários desafios, entre os quais: um quadro regulamentar fraco e fracamente implementado; a dificuldade de mobilização colectiva num sector íntimo, disperso, e ultra-explorado; um baixo nível de colaboração entre organizações de trabalhadores domésticos e a marginalização de organizações no contexto de um movimento sindical machista e de um movimento feminista classista. O estudo identifica algumas oportunidades, incluindo a ratificação da Convenção 189, a revisão de Lei de Trabalho, que pode criar uma abertura para reforçar o quadro regulamentar, e o reforço das organizações de trabalhadores domésticos e de colaborações estratégicas entre o movimento sindical e o movimento feminista. Porém, o estudo também identifica algumas ameaças, como a crise económica e financeira, que aumentou o custo de vida e aprofundou uma política de austeridade, a falta de vontade política por parte do Estado e a concorrência entre as organizações da sociedade civil. Com base nesta análise, o estudo apresenta as seguintes recomendações para o Estado e para o movimento sindical e feminista.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; employment / emprego; gender / género

Trabalho em Função do Género, Trabalho Migratório: Reformar os Regimos do Açúcar em Xinavane, Moçambique - Lazzarini, Alicia Hayashi (Desafios para Moçambique 2020, 2020)
O açúcar tem desempenhado um papel fundamental e controverso em Moçambique. Desde 1996, o Governo moçambicano e a iniciativa privada aproveitaram-se da ideia de que a África é a «última fronteira» do investimento (Diop et al., 2015; The Economist, 2013; Sizemore, 2012) para reinvestir numa economia devastada pela guerra civil e «reabilitá-la». Com um crescimento de sete por cento e, nos últimos anos, uma das taxas mais elevadas de investimento estrangeiro em África, Moçambique tem sido apresentado como um país posicionado para um crescimento explosivo. O açúcar tem desempenhado um papel crucial na transformação do presumível potencial da paisagem moçambicana em produtividade e na restauração da capacidade da nação para competir em mercados globais. A Açucareira de Xinavane tem sido o exemplo notável deste esforço de reabilitação. Antigamente conhecido como uma propriedade colonial menor, o actual empreendimento conjunto entre o Governo de Moçambique e a empresa sul-africana Tongaat Hulett tornou a Açucareira a maior plantação de açúcar do País. Entre 2005 e 2013, a área de cana-de-açúcar cultivada triplicou de 6000 para mais de 17 000 hectares (ha), com um aumento correspondente na produção de cana-de-açúcar, de 500 000 para 1,5 milhões de toneladas. A nova abordagem da produção de Xinavane enfatiza as técnicas de quantificação, cálculo e gestão originárias dos institutos de pesquisa de açúcar da África do Sul. Representantes da empresa e da indústria nacional descrevem a reabilitação da fábrica como a implementação directa da prática industrial padrão, apesar de enfrentar um contexto de «desenvolvimento» desafiador. Nas descrições do Governo e da indústria, o açúcar fornecerá empregos, infra- -estruturas necessárias e centros rurais com bancos, escolas e hospitais que beneficiarão todos os moçambicanos. Com este objectivo, foram levados a Xinavane peritos industriais regionais para formar gestores moçambicanos, supervisionar o restabelecimento e o crescimento da indústria e, finalmente, tornar possível o «progresso» económico e social de um país emergente de uma situação de conflito e, assim, construir uma economia capitalista competitiva. O presente artigo levanta questões sobre as tensões no seio desta abordagem tecnicamente estruturada. Analisa sobretudo as estratégias emergentes de gestão do trabalho, e identifica a forma como as «novas» práticas gerem uma força de trabalho grande e anteriormente indisciplinada. Esta gestão tem sido realizada através da divisão geográfica e de género, que não só reforça as baixas valorizações sociais e materiais da vida e do trabalho rural moçambicano, mas também restabelece um regime de trabalho profundamente associado à violência do passado colonial. Ao interrogar a dinâmica material e discursiva da «ciência da indústria» e da «tecnologia» na prática, ponho em causa os alegados impactos modernizadores desta abordagem «nova» no Moçambique pós-colonial.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; agriculture / agricultura; employment / emprego; gender / género

Redressing the gender imbalance: a qualitative analysis of recruitment and retention in Mozambique’s community health workforce - Steege, Rosalind; Taegtmeyer, Miriam; Ndima, Sozinho; Give, Celso; Sidat, Mohsin; Ferrão, Clara; Theobald, Sally (Human Resources for Health, 2020)
Findings: In-depth interviews (n = 30), key informant interviews (n = 1) and focus group discussions (n = 3) captured experiences and perceptions of employment processes. Intra-household decision-making structures mean women may experience additional barriers to join the APE programme, often requiring their husband’s consent. Training programmes outside of the community were viewed positively as an opportunity to build a cohort. However, women reported difficulty leaving family responsibilities behind, and men reported challenges in providing for their families during training as other income-generating opportunities were not available to them. These dynamics were particularly acute in the case of single mothers, serving both a provider and primary carer role. Differences in attrition by gender were reported: women are likely to leave the programme when they marry, whereas men tend to leave when offered another job with a higher salary. Age and geographic location were also important intersecting factors: younger male and female APEs seek employment opportunities in neighbouring South Africa, whereas older APEs are more content to remain. Conclusion: Gender norms, roles and power dynamics intersect with other axes of inequity such as marital status, age and geographic location to impact recruitment and retention of APEs in Maputo Province, Mozambique. Responsive policies to support gender equity within APE recruitment processes are required to support and retain a gender-equitable APE cadre.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - south / sul; GP - Maputo; Health PEA; L - english / inglês; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde; power / poder

Mozambique Annual Report 2020: Responding to a Year of Crisis - Wojnar, Andrea M; Lomelin, Jessica; Baker, Daniel; Salu, Karlina; Macangira, Assane; Manjate, Epidauro (UNFPA, 2020)
In the case of Mozambique, the pandemic came on the heels of two destructive cyclones that had devastated large parts of the country in 2019 and whose consequences were still being felt. In northern Mozambique, increasing violence in Cabo Delgado province resulted in a surge of internally displaced persons into local communities in Cabo Delgado, Nampula and Niassa provinces. With host communities ill equipped to meet the needs of those displaced, this population movement created a new humanitarian crisis in the midst of the pandemic. Like all of our governmental, civil society and donor partners, the resilience of UNFPA was tested, and we had to adjust quickly after the first case of COVID-19 was confirmed in March and the Government declared a state of emergency. At the most basic level, women continued to get pregnant and babies were still being born, even in the middle of a pandemic. Addressing the needs of adolescent girls and young women could not be put on hold. Helping to meet the needs of the symbolic target of UNFPA’s work – “the 10-year-old girl” – could not wait until she was 11. Helping to meet her aspirations for the future, advocating and working for her growth and self-fulfillment as a woman leading a healthy, productive and violence-free life – these could not wait a year.
Keywords: G - Mozambique / Moçambique; Health PEA; L - english / inglês; gender / género; health - COVID-19 / saúde – COVID-19; health / saúde; youth / juventude

Faith communities, youth and development in Mozambique - Chifeche, Victoria; Dreyer, Yolanda (HTS Teologiese Studies / Theological Studies, 2019)
In Mozambique, poverty is pervasive because of factors such as the civil war (1976–1992) and its aftermath, political instability, food scarcity and natural disasters. This article elucidates the situation of post-civil war Mozambique from a socio-political perspective with a specific focus on children and the youth as a particularly vulnerable group. Many children and young people have been displaced and are subject to work exploitation and sexual abuse. Female children also fall victim to the cultural practice of child marriage. The absence of comprehensive social measures for the protection of vulnerable young persons has a detrimental effect on their welfare and future prospects. The aim of the article is to explore the role that faith communities and church institutions can play in this context. From an inclusive congregational perspective, the inclusion of youth in all aspects of faith communities as a strategy for development is discussed. From a human rights and theological perspective, participatory action is required for faith communities and church institutions to contribute to making a life of human dignity possible for children and young people.
Keywords: *tagged; G - Mozambique / Moçambique; L - english / inglês; gender / género; institutions / instituições; youth / juventude

Regional Disparities in Fertility Preferences and Demand Satisfied for Family Planning by Modern Methods across Levels of Poverty - Assaf, Shireen; Wang, Wenjuan (USAID, 2019)
Research has highlighted disparities in family planning outcomes by wealth and by region separately. This analysis examines regional disparities within specific poverty groups. Twelve USAID family planning priority countries with recent DHS or AIS surveys were selected for the analysis, including 11 DHS surveys (Democratic Republic of Congo (DRC), Ethiopia, Ghana, Haiti, Malawi, Nepal, Nigeria, Pakistan, Rwanda Uganda, and Zambia) and one AIS survey (Mozambique). The measure of absolute poverty used in the analysis was comparable across the surveys. Households were divided into three groups to define the level of poverty: not extremely poor, extremely poor but not asset poor, and extremely poor and asset poor. Two outcomes were examined for women in union: ideal number of children and demand for family planning satisfied by modern contraceptive methods. The analysis examined regional disparities in these outcomes within each of the three poverty groups using descriptive statistics, maps, and regression analyses. The results showed patterns specific to individual countries. In some countries, including Haiti, Malawi, and Rwanda, few or no regional disparities were apparent. In others, one or a few clustered regions stood out from the rest by having worse outcomes across all poverty groups (for example, Somalia region in Ethiopia). Other countries showed more regional variability in just one of the three poverty groups. This was especially true in several countries for demand for family planning satisfied by modern methods among the extremely poor and asset poor group. These results highlight the need for family planning programs to focus on specific regions where disparities exist, and on poverty groups where little of the demand for family planning is satisfied by modern methods.
Keywords: #Reviews & Framing / Revisões e Organização; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; G - north / norte; Health PEA; L - english / inglês; Northern PEA; demographics / demografia; gender / género; health / saúde; poverty / pobreza

Conferência Internacional Sobre a Educação da Rapariga - ROSC (ROSC - Fórum da Sociedade Civil para os Direitos da Criança, 2019)
O Movimento de Educação para Todos (MEPT) em coordenação com o Ministério da Educação e Desenvolvimento Humano (MINEDH), realizou nos dias 6 e 7 de Junho do corrente ano, em Maputo, a Conferência Internacional Sobre a Educação da Rapariga com o lema “Desafios, Partilha de Experiências e Boas Práticas para Assegurar a Retenção da Rapariga no Sistema de Ensino.” Esta conferência tinha como objetivos: → Troca de experiências em torno de políticas e práticas existentes a nível nacional e internacional para assegurar a retenção da rapariga no sistema de ensino e discutir estratégias e possíveis soluções para a redução dos índices de abandono escolar por parte das raparigas na África Subsariana; → Apreciar os instrumentos e experiências existentes para prevenir a gravidez infantil e combater a violência baseada no género nas escolas a nível da região; → Olhar para os instrumentos e experiências existentes de boas práticas na região para o tratamento de casos de alunas grávidas nas escolas e a sua reintegração.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; education / educação; gender / género

Limits of gender equality: Poor, uneducated Mozambicans less likely to see improvement - Bhoojedhur, Sadhiska; Isbell, Thomas (AFR Barometer, 2019)
Gender equality is enshrined in Mozambique’s Constitution and promoted through its participation in international conventions and treaties as well as its 2004 Family Code, which requires equality in property and family law, including sharing of assets within marriage (International Federation for Human Rights, 2007; UN Women, 2012). During the launch of a National Plan of Action on Women, Peace, and Security in June 2018, the Minister of Gender, Children, and Social Welfare reiterated the government’s commitment to promoting gender equality, emphasizing that equal participation of men and women in all spheres of society is a prerequisite for sustainable development (AllAfrica, 2018). Yet gender disparities are a persistent reality for many women in Mozambique, in forms ranging from child marriage and teen pregnancy to domestic violence and sexual abuse (Cumbe, Materula, Sadler, & Agosta, 2017; Christensen, 2018). According to a United Nations Country Team report (2013), more than half of Mozambican women report having suffered some form of physical, sexual, or psychological violence, and almost three-fourths of girls said they were aware of cases of sexual abuse and harassment in their schools. Mozambique ranks 138th out of 164 countries on the United Nations Development Programme’s (2018) Gender Development Index, and especially in the North and in rural areas, traditional patriarchal values remain strong (Tvedten, 2011). In leadership roles, Mozambican women are better represented than women in many other African countries: 40% of the Mozambican Parliament are women (World Bank, 2018). However, while the Global Gender Gap Report ranked Mozambique No. 1 in Africa in 2008 in terms of economic participation and opportunity, by 2018 the country had dropped to No. 7 (No. 49 in the world) because of setbacks in women’s labour-force participation, particularly in senior and managerial positions (World Economic Forum, 2008, 2018). According to the latest Afrobarometer survey, a majority of Mozambicans think gender equality has been achieved with regard to education, work, and land, and give the government good marks on promoting opportunities for women. However, poor and lesseducated citizens are considerably less likely to perceive progress on gender equality. Moreover, Mozambicans’ support for equality is uneven: While most endorse equality in access to land and political leadership, majorities prioritize men when it comes to getting a job and say families are better off if a woman, rather than a man, takes care of home and children.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; education / educação; gender / género; poverty / pobreza

Impacto Dos Conflitos Armados Na Vida Das Mulheres e Raparigas Em Moçambique: Relatório Da Pesquisa De Campo Nas Províncias De Nampula, Zambézia, Sofala E Gaza - Lawyers Without Borders (Lowyers Without Borders, 2019)
O presente estudo pretende entender como a violência político-militar no país afectou as mulheres e as raparigas e que medidas foram tomadas de forma a apoiar as mulheres víctimas da violência. O estudo visa trazer à luz os diferentes tipos de violações de direitos humanos e de violência cometidos contra as mulheres e raparigas no contexto dos conflitos armados considerando que, e segundo Moura, Silva et all (2012) “A inexistência de dados, estudos e análises sobre violências (directas) contra mulheres e jovens do sexo feminino na Guiné-Bissau, Angola e em Moçambique, torna difícil a tarefa de traçar com precisão uma tipologia das violências cometidas contra estes grupos, ou aferir a sua evolução no pós-conflito armados”. Em termos de actores, o estudo privilegiou, entre outros aspectos, a análise dos principais perpetradores e as suas motivações, entre outros aspectos como forma de definir o perfil das víctimas do conflito armado usando critérios como a faixa etária, o gênero, grau de escolaridade, estado civil, filhos e perfil social e económico. Por outro lado, e considerando o papel da mulher como um factor importante na sociedade, o estudo analisou igualmente a participação directa ou indirecta das mulheres no conflito armado moçambicano cuja maior tónica incidiu sobre a guerra dos 16 anos. No final, o estudo identificou propostas de medidas de reparação – de carácter individual e colectivo derivados das consequências dos conflitos armados na vida de mulheres e raparigas em Moçambique a partir da escuta das reivindicações das próprias víctimas.
Keywords: G - Mozambique / Moçambique; G - central / centro; G - north / norte; G - south / sul; GP - Gaza; GP - Nampula; GP - Sofala; GP - Zambézia; L - portuguese / português; conflict / conflito; gender / género

The State of ICT in Mozambique 2018 - Gillwald, Alison; Mothobi, Onkokame; Rademan, Broc (Research ICT Africa, 2019)
Mozambique has a challenging path ahead if it is to realise the full potential of the ICT sector in developing its economy and to make progress on the information communication technology targets that are intended as enabling the achievement of the United Nations’ Sustainable Development Goals. Mozambique’s successes include licensing and regulatory achievements in telecommunications, which have stimulated competition and contributed to meeting national policy objectives.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; access to services / acesso a serviços; gender / género; infrastructure - energy / infrastrutura - energia; infrastructure / infrastrutura

Midwives’ perspectives on (dis)respectful intrapartum care during facility-based delivery in sub-Saharan Africa: a qualitative systematic review and meta-synthesis - Bradley, Susan; McCourt, Christine; Rayment, Juliet; Parmar, Divya (Reproductive Health, 2019)
Background: In the past decade, the negative impact of disrespectful maternity care on women’s utilisation and experiences of facility-based delivery has been well documented. Less is known about midwives’ perspectives on these labour ward dynamics. Yet efforts to provide care that satisfies women’s psycho-socio-cultural needs rest on midwives’ capacity and willingness to provide it. We performed a systematic review of the emerging literature documenting midwives’ perspectives to explore the broader drivers of (dis)respectful care during facility-based delivery in the sub-Saharan African context. Methods: Seven databases (CINAHL, PsychINFO, PsychArticles, Embase, Global Health, Maternity and Infant Care and PubMed) were systematically searched from 1990 to May 2018. Primary qualitative studies with a substantial focus on the interpersonal aspects of care were eligible if they captured midwives’ voices and perspectives. Study quality was independently assessed by two reviewers and PRISMA guidelines were followed. The results and findings from each study were synthesised using an existing conceptual framework of the drivers of disrespectful care. Results: Eleven papers from six countries were included and six main themes were identified. ‘Power and control’ and ‘Maintaining midwives’ status’ reflected midwives’ focus on the micro-level interactions of the mother-midwife dyad. Meso-level drivers of disrespectful care were: the constraints of the ‘Work environment and resources’; concerns about ‘Midwives’ position in the health systems hierarchy’; and the impact of ‘Midwives’ conceptualisations of respectful maternity care’. An emerging theme outlined the ‘Impact on midwives’ of (dis)respectful care. Conclusion: We used a theoretically informed conceptual framework to move beyond the micro-level and interrogate the social, cultural and historical factors that underpin (dis)respectful care. Controlling women was a key theme, echoing women’s experiences, but midwives paid less attention to the social inequalities that distress women. The synthesis highlighted midwives’ low status in the health system hierarchy, while organisational cultures of blame and a lack of consideration for them as professionals effectively constitute disrespect and abuse of these health workers. Broader, interdisciplinary perspectives on the wider drivers of midwives’ disrespectful attitudes and behaviours are crucial if efforts to improve the maternity care environment - for women and midwives - are to succeed.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Maputo City / Cidade de Maputo; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; G - south / sul; GP - Maputo; Health PEA; L - english / inglês; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde; power / poder

Religion and Use of Institutional Child Delivery Services: Individual and Contextual Pathways in Mozambique - Cau, Boaventura Manuel; Agadjanian, Victor (International perspectives on sexual and reproductive health, 2019)
CONTEXT: Research on institutional child delivery in Sub-Saharan Africa typically focuses on availability and accessibility of health facilities. Cultural factors, including religion, that may facilitate or hinder the use of such services have not been well examined and remain poorly understood. METHODS: The relationship between religious affiliation and delivery in a health facility was explored using data from a household survey of 1,297 women aged 18-50 and a census of 825 religious congregations, both conducted in a predominantly Christian district in Mozambique in 2008. Multilevel logistic regression analyses were conducted to predict the likelihood of recent institutional delivery according to both individual religious affiliation and the concentration of religious congregations of certain denominations in the community of residence. RESULTS: Approximately 63% of deliveries occurred in a health facility. The odds of such deliveries were lower among women who belonged to Apostolic churches or had no religious affiliation than among members of Catholic or mainline Protestant churches, net of other factors (odds ratios, 0.5 and 0.6, respectively). In addition, regardless of a woman's religion, the odds that she had an institutional delivery increased by 9% for each additional Catholic or mainline Protestant congregation in her community of residence (1.1). CONCLUSIONS: Organized religion is associated with critical health outcomes in Mozambique and, potentially, in other Sub-Saharan African contexts. Policymakers should consider designing programs and interventions that promote the use of institutional delivery services among members of religious groups characterized by low use of these services and in areas where such religious groups have a strong presence.
Keywords: G - Mozambique / Moçambique; L - english / inglês; access to services / acesso a serviços; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde

Health equity monitoring is essential in public health: lessons from Mozambique - Llop-Gironés, Alba; Cash-Gibson, Lucinda; Chicumbe, Sergio; Alvarez, Francesc; Zahinos, Ivan; Mazive, Elisio; Benach, Joan (Globalization and Health, 2019)
Background: Countries must be able to describe and monitor their populations health and well-being needs in an attempt to understand and address them. The Sustainable Development Goals (SDGs) have re-emphasized the need to invest in comprehensive health information systems to monitor progress towards health equity; however, knowledge on the capacity of health information systems to be able do this, particularly in low-income countries, remains very limited. As a case study, we aimed to evaluate the current capacity of the national health information systems in Mozambique, and the available indicators to monitor health inequalities, in line with SDG 3 (Good Health and Well Being for All at All Ages). Methods: A data source mapping of the health information system in Mozambique was conducted. We followed the World Health Organization’s methodology of assessing data sources to evaluate the information available for every equity stratifier using a three-point scale: 1 - information is available, 2 - need for more information, and 3 an information gap. Also, for each indicator we estimated the national average inequality score. Results: Eight data sources contain health information to measure and monitor progress towards health equity in line with the 27 SDG3 indicators. Seven indicators bear information with nationally funded data sources, ten with data sources externally funded, and ten indicators either lack information or it does not applicable for the matter of the study. None of the 27 indicators associated with SDG3 can be fully disaggregated by equity stratifiers; they either lack some information (15 indicators) or do not have information at all (nine indicators). The indicators that contain more information are related to maternal and child health. Conclusions: There are important information gaps in Mozambique’s current national health information system which prevents it from being able to comprehensively measure and monitor health equity. Comprehensive national health information systems are an essential public health need. Significant policy and political challenges must also be addressed to ensure effective interventions and action towards health equity in the country.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; Health PEA; L - english / inglês; gender / género; health - health information systems / saúde - sistema de informação de saúde; health - maternal and child / saúde - materno-infantil; health - social determinants of health / saúde - determinantes sociais da saúde; health / saúde

Obstacles to advancing women’s health in Mozambique: a qualitative investigation into the perspectives of policy makers - Qiu, Mary; Sawadogo-Lewis, Talata; Ngale, Katia; Cane, Réka Maulide; Magaço, Amilcar; Roberton, Timothy (Global Health Research and Policy, 2019)
Background: Despite substantial investment in women’s health over the past two decades, and enthusiastic government support for MDG 5 and SDG 3, health indicators for women in Mozambique remain among the lowest in the world. Maternal mortality stayed constant from 2003 to 2011, with an MMR of 408; the estimated HIV prevalence for women of 15–24 years is over twice that for men; and only 12.1% of women are estimated to be using modern contraception. This study explores the perspectives of policy makers in the Mozambican health system and affiliates on the challenges that are preventing Mozambique from achieving greater gains in women’s health. Methods: We conducted in-depth interviews with 39 senior- and mid-level policy makers in the Ministry of Health and affiliated institutions (32 women, 7 men). Participants were sampled using a combination of systematic random sampling and snowball sampling. Participants were asked about their experiences formulating and implementing health policies and programs, what is needed to improve women’s health in Mozambique, and the barriers and opportunities to achieving such improvement. Results: Participants unanimously argued that women’s health is already sufficiently prioritized in national health policies and strategies in Mozambique; the problem, rather, is the implementation and execution of existing women’s health policies and programs. Participants raised challenges related to the policy making process itself, including an ever-changing, fragmented decision-making process, lack of long-term perspective, weak evaluation, and misalignment of programs across sectors. The disproportionate influence of donors was also mentioned, with lack of ownership, rapid transitions, and vertical programming limiting the scope for meaningful change. Finally, participants reported a disconnect between policy makers at the national level and realities on the ground, with poor dissemination of strategies, limited district resources, and poor consideration of local cultural contexts. Conclusions: To achieve meaningful gains in women’s health in Mozambique, more focus must be placed on resolving the bottleneck that is the implementation of existing policies. Barriers to implementation exist across multiple health systems components, therefore, solutions to address them must also reach across these multiple components. A holistic approach to strengthening the health system across multiple sectors and at multiple levels is needed.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; Health PEA; L - english / inglês; access to services / acesso a serviços; gender / género; government policy / politica governamental; health - dignified care / saúde - atendimento humanizado / mau atendimento; health - maternal and child / saúde - materno-infantil; health / saúde

Impacto das Uniões Prematuras na Educação, Saúde e Nutrição em Moçambique: Resumo do Documento - ROSC (ROSC - F;orum da Sociedade Civil para os Direitos da Criança, 2019)
As uniões prematuras constituem um dos principais problemas sociais na África Austral que, pelas suas consequências negativas em cadeia: gravidez precoce,desnutrição crónica,fístula obstétrica,abandono escolar,se tornam um problema igualmente económico, uma barreira ao desenvolvimento socioeconómico. No caso de Moçambique, o problema afecta cerca de metade das raparigas com menos de 18 anos, o que faz do país um dos cinco mais afectados a nível da Comunidade dos Países da África Austral (SADC). Para fazer face a este problema, várias acções têm sido levadas a cabo, entre campanhas de sensibilização, programas de resgate de meninas em situação de vida marital precoce, lobby e advocacia para o fortalecimento do quadro institucional e legal, bem como estudos para melhor informar as acções referidas. No entanto, quase todas as pesquisas feitas à volta das uniões prematuras têm sido na perspectiva sociológica ou antropológica. Por isso, o Fórum da Sociedade Civil para os Direitos da Criança (ROSC), no âmbito das acções da Coligação para a Eliminação dos Casamentos Prematuros (CECAP), com o apoio da OXFAM, através do Programa AGIR, decidiu realizar este estudo de perspectiva económica, para aferir o impacto que as uniões prematuras têm na educação, saúde e nutrição no país. Este estudo foi elaborado com quatro finalidades: primeira, contribuir para o debate sobre o impacto das uniões prematuras; segunda, elucidar aos actores-chave sobre as consequências das uniões prematuras para o desenvolvimento do país; terceira, despertar a consciência dos tomadores de decisão e da sociedade no geral sobre os impactos negativos das uniões prematuras na educação, saúde e nutrição; quarta e última finalidade, contribuir para despertar a atenção para a necessidade do desenho de programas, políticas e leis que visam mitigar os impactos negativos das uniões prematuras
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; education / educação; gender / género; health / saúde

Gender Roles, Relationships and Social Equity in Post-Harvest Management in Mozambique - FANRPAN (ood, Agriculture and Natural Resources Policy Analysis Network, 2018)
Key Recommendations: 1. Gender and other general policies in the agricultural sector should be revised to reflect clear priorities for lowering post-harvest losses (PHL). 2. Crop scientists should be trained and crop-specific PHM research infrastructure should be developed so that PHM can be included as a research component for all crops. 3. Academic and research units should be located in the field, close to the farmers, so that researchers and/or university students are closer to the beneficiaries. 4. PHM programs, projects, and activities must include information and technology development and dissemination relevant to the end-users, including women, children, the youth, and poorer farmers. 5. PHL should be reduced by increasing access to carts/wheelbarrows and their respective repair kits and to draught animals, repairing critical sections of rural roads, and increasing farmers’ access to bags/sacks that are not infested and in good condition. 6. Reduce PHL along the value chain from farm to plate by extending innovations to some of the socially perceived “female-roles” of PHM. 7. Development and dissemination of PHM innovations must also be part of policies, strategies, and practices to promote a better workload distribution by increasing male participation in labourdemanding PHM activities culturally assigned to women. 8. Since women in polygamous marriages and single mothers are easier to work with when it comes to promoting investment in PHM improvements due to their decision-making power in the households, they should be given priority in work plans. 9. Prioritize female farmers in PHM capacity-building initiatives, because they are the ones who deal with most of the PHM activities. 10. Local tools manufacturers should benefit from incentives to lower the cost for the development of manufacturing, processing, and packaging equipment to make them accessible to women and the poor.
Keywords: G - Mozambique / Moçambique; L - english / inglês; agriculture / agricultura; gender / género

O processo de empoderamento das raparigas em Marrere - Estudo de caso do Projeto Mwarusi - Eloisa Nair Lopes da Costa (Instituto Universitário de Lisboa, 2018)
Desde o Acordo Geral de Paz, assinado em 1992, Moçambique realizou reformas políticas de intervenção no combate à pobreza. Contudo, em 2006, verificou-se que 54% da população moçambicana ainda se encontrava abaixo da linha de pobreza. Foi então que, Moçambique, em parceria com organizações internacionais iniciou os seus esforços na promoção de programas centrados na igualdade e equidade de género e a sua atuação junto de comunidades mais vulneráveis, tendo em conta particularmente a educação e a saúde. Para estes avanços contribuíram os Objetivos de Desenvolvimento do Milénio e o Plano de Ação para a redução da pobreza absoluta. O estudo de caso desenvolvido nesta dissertação tem como objetivo compreender o modo pelo qual o Projeto Mwarusi, implementado pela Girl Move Foundation, contribui para um empoderamento efetivo das raparigas no bairro de Marrere em Nampula, Moçambique, compreender o seu impacto na comunidade e a sua aplicabilidade a outras comunidades e grupos. Para compreender o Projeto Mwarusi e, em particular, a situação da mulher moçambicana e as políticas de promoção de igualdade, equidade e empoderamento existentes em Moçambique, foi necessário realizar-se uma análise multivariada que nos permitiu obter um conhecimento não só teórico, ao nível das perspetivas em questão, como prático que nos deu a oportunidade de conhecer a comunidade, a sua cultura e as suas tradições. Esta investigação tem, então, como objetivo a análise do Projeto Mwarusi, através de uma observação participante ao longo das sessões do projeto, através da realização de entrevistas semiestruturadas e questionários on-line aplicados a seis guias, a oito mentoras do Projeto Mwarusi, o que nos permitirá avaliar o sucesso e impacto do Projeto Mwarusi e, por último, através do acompanhamento do desenvolvimento do projeto entre 2015 e 2018.
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Nampula; L - portuguese / português; empowerment / empoderamento; gender / género; youth / juventude

National Action Plan on Women, Peace, and Security (2018-2022) - República de Moçambique / Republic of Mozambique Ministry of Gender, Child and Social Action (2018)
Main plan objectives include legislation re women, peace, security; integrating gender perspectives in all actions re: conflict prevention/management; guarantee participation of women in decision making, structures in peace and security processes; promoting mechanisms to secure increased recruitment, retention, promotion of women in defense, security, justice sectors; reinforce fights against all forms of violence against women/girls in armed and non-armed conflict; expanding efforts for security, physical and mental health and dignity of women and girls; securing rights of women and girl in conflict and post-conflict situations. Plan's main objectives align with the Southern Africa Development Community's Regional Strategy on women, peace, and seucirty (2018-2022).
Keywords: #Policy Document / Documento de Política; *tagged; G - Mozambique / Moçambique; L - english / inglês; gender / género; government policy / politica governamental

Principais Resultados do IMASIDA 2015 - INE; INS; ICF (Instituto Nacional de Saúde (INS), Instituto Nacional de Estatística (INE), e ICF, 2018)
O Inquérito de Indicadores de Imunização, Malária e HIV/SIDA (IMASIDA 2015) em Moçambique foi realizado no âmbito de The DHS Program e vem no seguimento de quatro inquéritos anteriores, com o objectivo de determinar indicadores de saúde da mulher e da criança no país, tais como a fecundidade; gravidez e maternidade na adolescência; preferências de fecundidade; planeamento familiar; consultas pré-natais; assistência ao parto; vacinação de crianças; infecções respiratórias agudas; diarreia e tratamento das diarreias; anemia; práticas alimentares em crianças com diarreia; aleitamento em crianças; posse e uso de redes mosquiteiras; tratamento de crianças com febre; prevalência da malária e anemia nas crianças; conhecimento, atitudes e comportamentos em relação ao HIV/SIDA e cobertura de serviços de testagem de HIV; prevalência de HIV e outros indicadores associados como: o acesso e tratamento da água, saneamento básico, educação ou frequência escolar, emprego, idade na primeira união e na primeira relação sexual, empoderamento da mulher e violência baseada no género.
Keywords: G - Mozambique / Moçambique; G - north / norte; Health PEA; L - english / inglês; M - survey / inquérito; Northern PEA; demographics / demografia; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde

MUVA Urban Youth Survey: A statistical profile of urban youth in Maputo and Beira, Mozambique - Arau, Andres; Bhalla, Garima; Bischler, Jana; Jasper, Paul (MUVA / OPM, 2018)
The MUVA Urban Youth Survey was conducted as part of the research activities for MUVA, a five-year DFID-funded female economic empowerment programme in urban Mozambique. MUVA works toward testing and finding solutions to help women and girls access opportunities to decent work by addressing the constraints they face. The objective of the survey is to obtain a statistical profile of the youth living in the MUVA target areas in Maputo and Beira to help inform policies about female economic empowerment and connected areas such as education, youth employment, family planning, and financial and digital inclusion. The survey covers a variety of thematic areas such as education, employment and economic activities, financial inclusion, fertility and family planning, time use, social norms, social capital, and digital inclusion. The analysis in this report places a focus on the different constraints young women face compared to young men, especially with regards to how this affects their ability to participate in the labour market. This report is the first in a series of publications on this survey. It summarises key findings across all subject areas. Shorter, less technical thematic briefs will be produced as part of the dissemination activities. A technical compendium will be accompanying this report with all relevant statistical/technical information.
Keywords: G - Maputo City / Cidade de Maputo; G - Mozambique / Moçambique; GD - Beira; GP - Maputo; L - english / inglês; M - survey / inquérito; gender / género; youth / juventude

Empregados do Quintal (male domestic workers) in Nampula City: Domestic work, masculinities and matrilinearity - Humbane, Jossias Helder Jamisse (2018)
This study questions why domestic work that is generally considered a feminine job is yet a field dominated by men in the city of Nampula, Mozambique. In the attempt to explain this phenomenon, the research explores economic, social and cultural aspects. Due to the fact that Nampula is a province with a strong Islamic presence and the majority of the population identify themselves as belonging to the Makhuwa ethnic group—which is traditionally defined by a matrilinear kinship system—I argue that the domestic sector remaines masculinised because of the influence of the matrilinear values and gendered practices. I also argue that the Islamic patriarchal values play a decisive role as men see themselves as the exclusive family providers and for that reason forbid their wives to develop and to get engaged in economic activities outside the household. This study also explores notions of masculinity in connection with domestic work and examines how male domestic workers, coming from rural areas and employed in the city, perceive and perform their masculine identities. How does the job of the domestic worker shape particular understandings of masculinity? Given the fact that many domestic workers in Nampula are immigrant people from the rural areas of the Zambézia province, I argue that migrating and working in the city is considered as a way to achieve a manhood as immigrants have access to goods that can only be purchased in urban contexts and are scarce in the villages. The access to all these “modern” commodities and the experience of the city make the immigrant young boys to gain respect in their original communities.
Accepted: 2019-04-12T09:43:27Z Publisher: University of the Western Cape
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; L - english / inglês; employment / emprego; gender / género

How do gender relations affect the working lives of close to community health service providers? Empirical research, a review and conceptual framework - Steege, Rosalind; Taegtmeyer, Miriam; McCollum, Rosalind; Hawkins, Kate; Ormel, Hermen; Kok, Maryse; Rashid, Sabina; Otiso, Lilian; Sidat, Mohsin; Chikaphupha, Kingsley; Datiko, Daniel Gemechu; Ahmed, Rukhsana; et al. (Social Science & Medicine, 2018)
Close-to-community (CTC) providers have been identiﬁed as a key cadre to progress universal health coverage and address inequities in health service provision due to their embedded position within communities. CTC providers both work within, and are subject to, the gender norms at community level but may also have the potential to alter them. This paper synthesises current evidence on gender and CTC providers and the services they deliver.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; Health PEA; L - english / inglês; access to services / acesso a serviços; gender / género; government policy / politica governamental; health - maternal and child / saúde - materno-infantil; health / saúde

Regional disparities in fertility preferences and demand for family planning satisfied by modern methods across levels of poverty: Mozambique An Analysis Brief from The DHS Program - USAID (USAID, 2018)
The DHS Analytical Studies 71 examines subnational variations in fertility preferences and family planning outcomes associated with poverty in married women in 12 recent Demographic and Health Surveys. Poverty is measured based on a standard set of criteria for unsatisfied basic needs and the ownership of specific assets. Households are categorized into three poverty groups: not extremely poor, extremely poor but not asset poor, and extremely poor and asset poor. This brief summarizes the results from the Democratic Republic of The Congo based on the 2013-14 DHS on regional variations in poverty, regional estimates of mean ideal number of children, and demand for family planning satisfied by modern methods, for each poverty group among married women.
Keywords: #Reviews & Framing / Revisões e Organização; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; G - north / norte; Health PEA; L - english / inglês; Northern PEA; demographics / demografia; gender / género; health / saúde; poverty / pobreza

Maternal and Newborn Mortality: Community Opinions on Why Pregnant Women and Newborns Are Dying In Natikiri, Mozambique - Belo, C; Pires, P; Josaphat, J; Siemens, R; Rooke, E; Spence-Gress, C (International Journal of Research, 2017)
Background and objective: maternal and neonatal mortality rates in Mozambique are high, due to insufficient numbers of qualified health workers, lack of equipment and materials, referral system deficiency, difficulties to access health services and gender issues. This study assesses the barriers to health care access, regular attendance at ante natal consultations, institutional delivery and postnatal and neonatal follow-up. This is part of the baseline study for an implementation research project to reduce maternal and neonatal mortality in Natikiri, Nampula, Mozambique. Conclusion: local community members and health professionals were asked to state what they thought would be the best way to intervene. These ideas were then discussed further at a conference with health professionals and government representatives. Six intervention strategies to address identified problems were decided on and will be the basis for the ongoing implementation research project. They were: 1. Expanding family planning especially with adolescents. 2. Community based transport system for pregnant women. 3. Strengthening maternal and child health services by training maternity personnel in obstetrical emergency care and neonatal resuscitation. 4. Providing four quality prenatal visits. 5. Providing quality cesarean deliveries. 6. Supporting the Mozambican Government's campaign against bribery.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; Health PEA; L - english / inglês; access to services / acesso a serviços; gender / género; health - dignified care / saúde - atendimento humanizado / mau atendimento; health - maternal and child / saúde - materno-infantil; health / saúde; ⛔ No DOI found

Maternity care system in Maputo, Mozambique: Plans and practice? - Long, Qian; Madede, Tavares; Parkkali, Saara; Chavane, Leonardo; Sundby, Johanne; Hemminki, Elina (Cogent Medicine, 2017)
Mixed methods were used with various data sources to describe organisation and delivery of maternity care in Maputo city, Mozambique in early 2010s and to compare the plans with the service provision in practice. In the public health sector, maternity care was organised to be area based and hierarchical with a planned referral system. The provision of basic and emergency maternity care was publicly funded, largely dependent of donor funds, and free of charge for users. Even though Maputo City was better resourced than the rest of the country, there was a large lack of health professionals. Women’s choices and self-referrals, even to higher levels of care, were common, which broke the plans of areas responsibility, gate keeping and care by medical needs. Private services for maternity care had emerged for those who were able to pay, leading to dual practices of health professionals and shortage of care providers in the public system at odd hours. Information of maternity care was aggregate and poorly stored. The gap between “planned” services delivery and “practice” in a real-life requires overall health system strengthening to improve efficiency and effectiveness of health services delivery.
Keywords: *indexed; *tagged; G - Maputo City / Cidade de Maputo; G - Mozambique / Moçambique; G - south / sul; GP - Maputo; Health PEA; L - english / inglês; access to services / acesso a serviços; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde

Perspectives on the coordination of multisectoral nutrition in Mozambique and an emerging framework - Michaud-Létourneau, Isabelle; Pelletier, David Louis (Food Policy, 2017)
Multisectoral approaches represent a prominent ideological consensus, inﬂuenced by historical roots and the current political, ﬁnancial and institutional landscape, to address the multi-faceted and complex causes of most nutrition, public health and food problems. However, the implementation of multisectoral approaches presents tremendous challenges; one of the most often cited problems, in the literature and by practitioners, is coordination. This study investigates the perspectives of key national leaders on a range of issues regarding the coordination of a Multisectoral Action Plan for the Reduction of Chronic Undernutrition (PAMRDC) in Mozambique. Within this policy group, the principal researcher played the role of a researcher-participant for 14 months, and used Q methodology with a total of 21 key national leaders who had been actively engaged in coordination groups at the central level. Participants sorted 54 subjective statements on a range of issues that were present in the current national discourse. The results revealed four distinct perspectives. The Implementation perspective (n = 12) prioritized concrete actions to advance the operationalization of the plan, based on a guidance-based approach from the central level to the lower administrative levels. The Advocacy perspective (n = 3) emphasized advocacy to increase politicians’ awareness of the problem and of potential solutions to enhance political commitment. The Structuralist perspective (n = 3) was concerned with the development of structures and mechanisms to facilitate coordination, funding and improving communication between the government and donors. The People-centered perspective (n = 3) focused on the importance of mobilizing individuals to compensate for the sub-optimal structures and processes for coordination. Areas of convergence across the perspectives included: low capacity and skills that limit the work; the agency in charge of coordination (SETSAN) should exercise an increased leadership to facilitate the multisectoral work; and SETSAN should advocate to mobilize politicians and donors for resources. Areas of divergence related to the type of guidance from national to sub-national levels (prescriptive or not) and the functions to be carried out by SETSAN. This study highlights lack of clarity on the meaning of coordination and on the functions of the multisectoral coordination body that appear to arise for two reasons: the lack of an explicit and shared framework for the policy process and the complex nature of coordination itself. These results are examined through the lenses of several related literatures, including governance, public policy and political economy of nutrition, leading to a three-dimensional conceptual framework for coordination that distinguishes the coordination space, forms, and instruments. Global guidance, such as provided through the SUN movement, could support countries in overcoming their coordination challenges by facilitating an analysis of their decision-making processes in order to choose the functions for the coordination body based on a shared understanding of countries’ needs, context and opportunities. This paper moves the ﬁeld beyond a broad consideration of horizontal and vertical coordination within multisectoral initiatives.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; Health PEA; L - english / inglês; gender / género; government policy / politica governamental; health - maternal and child / saúde - materno-infantil; health / saúde

Reality checks in Mozambique: building better understanding of the dynamics of poverty and well-being. Final Report 2011-2015 - Tvedten, Inge; Tuominen, Minna; Rosário, Carmeliza (ORGUT Consulting AB, 2016)
A series of five “Reality Checks” will take place in the period 2011-2016, focussing on the dynamics of poverty and well-being with a particular focus on good governance, agriculture/climate and energy that are key sectors in Swedish development cooperation with Mozambique. Each Reality Check will be published in the form of one Annual Report and three Sub-Reports from each of the three selected study-sites (see ORGUTa 2011 for more details). More concretely, the “Reality Checks in Mozambique” are expected to: i) Inform the public discussion among key development actors on poverty reduction, especially in the province of Niassa; ii) Contribute to a better understanding of qualitative poverty monitoring methods in Mozambique; iii) Provide Sweden with relevant qualitative data on developments and results from its engagement in Mozambique and support further implementation of its programme in Niassa. The series of studies was initiated by an Inception Report published in August 2011 (ORGUT 2011a). Through that exercise, it was decided that the Reality Checks shall be based on fieldwork in three different Districts/Municipalities in the Province of Niassa that display variations in terms of geographical locations, access to public services and levels of poverty and well-being. The three areas selected were i); the Municipality of Cuamba; ii) the District of Lago and iii) the District of Majune (see Map 1). The 1 st Reality Check was carried out in 2011 in the form of three sub-reports (Orgut 2011 b,c,d) and the first Annual Report (Orgut 2011 e), and represent a baseline upon which the subsequent Reality Checks will build. This is the Annual Report for the 2 nd Reality Check, synthesising the main findings from the Cuamba, Lago and Majune sub-reports. In addition to pursuing the overall issue of the dynamics of poverty and well-being, this year’s reports have a thematic focus on governance.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Cuamba; GD - Lago; GD - Majune; GP - Niassa; L - english / inglês; M - evaluation / avaliação; agriculture / agricultura; gender / género; institutions / instituições; poverty / pobreza; private sector / setor privado

Reality checks in Mozambique – Building better understanding of the dynamics of poverty and well-being. Year Five, 2015, Sub-Report, District of Lago. - Tvedten, Inge; Putile, Beatriz; José, Barnabé; Paulo, Margarida (ORGUT Consulting AB, 2016)
The Reality Checks are implemented 2011-2016 and each year field work is carried out in the Municipality of Cuamba, the District of Lago and the District of Majune in the Niassa Province. Each Reality Check focusses on a specific theme. This is the 5th Sub-Report from the District of Lago, focussing on quantitative expressions of changes in poverty and wellbeing and the role of public institutions since the 1st Reality Check in 2011. An Annual Report is produced each year to summarise the findings and conclusions from the three subreports.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; GD - Lago; L - english / inglês; gender / género; poverty / pobreza

Place, Time and Experience: Barriers to Universalization Of Institutional Child Delivery in Rural Mozambique - Agadjanian, Victor; Yao, Jing; Hayford, Sarah R (International perspectives on sexual and reproductive health, 2016)
CONTEXT: Although institutional coverage of childbirth is increasing in the developing world, a substantial minority of births in rural Mozambique still occur outside of health facilities. Identifying the remaining barriers to safe professional delivery services can aid in achieving universal coverage. METHODS: Survey data collected in 2009 from 1,373 women in Gaza, Mozambique, were used in combination with spatial, meteorological and health facility data to examine patterns in place of delivery. Geographic information system-based visualization and mapping and exploratory spatial data analysis were used to outline the spatial distribution of home deliveries. Multilevel logistic regression models were constructed to identify associations between individual, spatial and other characteristics and whether women's most recent delivery took place at home. RESULTS: Spatial analysis revealed high- and low-prevalence clusters of home births. In multivariate analyses, women with a higher number of clinics within 10 kilometers of their home had a reduced likelihood of home delivery, but those living closer to urban centers had an increased likelihood. Giving birth during the rainy, high agricultural season was positively associated with home delivery, while household wealth was negatively associated with home birth. No associations were evident for measures of exposure to and experience with health institutions. CONCLUSIONS: The results suggest the need for a comprehensive approach to expansion of professional delivery services. Such an approach should complement measures facilitating physical access to health institutions for residents of harder-to-reach areas with community-based interventions aimed at improving rural women's living conditions and opportunities, while also taking into account seasonal and other variables.
Keywords: G - Mozambique / Moçambique; L - english / inglês; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde

Barriers and facilitators to health care seeking behaviours in pregnancy in rural communities of southern Mozambique - Munguambe, Khátia; Boene, Helena; Vidler, Marianne; Bique, Cassimo; Sawchuck, Diane; Firoz, Tabassum; Makanga, Prestige Tatenda; Qureshi, Rahat; Macete, Eusébio; Menéndez, Clara; von Dadelszen, Peter; Sevene, Esperança (Reproductive Health, 2016)
Background: In countries, such as Mozambique, where maternal mortality remains high, the greatest contribution of mortality comes from the poor and vulnerable communities, who frequently reside in remote and rural areas with limited access to health care services. This study aimed to understand women’s health care seeking practices during pregnancy, taking into account the underlying social, cultural and structural barriers to accessing timely appropriate care in Maputo and Gaza Provinces, southern Mozambique. Methods: This ethnographic study collected data through in-depth interviews and focus group discussions with women of reproductive age, including pregnant women, as well as household-level decision makers (partners, mothers and mothers-in-law), traditional healers, matrons, and primary health care providers. Data was analysed thematically using NVivo 10. Results: Antenatal care was sought at the heath facility for the purpose of opening the antenatal record. Women without antenatal cards feared mistreatment during labour. Antenatal care was also sought to resolve discomforts, such as headaches, flu-like symptoms, body pain and backache. However, partners and husbands considered lower abdominal pain as the only symptom requiring care and discouraged women from revealing their pregnancy early in gestation. Health care providers for pregnant women often included those at the health facility, matrons, elders, traditional birth attendants, and community health workers. Although seeking care from traditional healers was discouraged during the antenatal period, they did provide services during pregnancy and after delivery. Besides household-level decision-makers, matrons, community health workers, and neighbours were key actors in the referral of pregnant women. The decision-making process may be delayed and particularly complex if an emergency occurs in their absence. Limited access to transport and money makes the decision-making process to seek care at the health facility even more complex.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - south / sul; GP - Gaza; GP - Maputo; Health PEA; L - english / inglês; access to services / acesso a serviços; gender / género; health - dignified care / saúde - atendimento humanizado / mau atendimento; health - maternal and child / saúde - materno-infantil; health / saúde

Mapping the use of research to support strategies tackling maternal and child health inequities: evidence from six countries in Africa and Latin America - Vargas, Emily; Becerril-Montekio, Victor; Gonzalez-Block, Miguel Ángel; Akweongo, Patricia; Hazel, Cynthia N. A.; Cuembelo, Maria de Fatima; Limbani, Felix; Bernardo, Wanderley; Muñoz, Fernando (Health Research Policy and Systems, 2016)
Background: Striving to foster collaboration among countries suffering from maternal and child health (MCH) inequities, the MASCOT project mapped and analyzed the use of research in strategies tackling them in 11 low- and middle-income countries. This article aims to present the way in which research influenced MCH policies and programs in six of these countries – three in Africa and three in Latin America. Methods: Qualitative research using a thematic synthesis narrative process was used to identify and describe who is producing what kind of research, how research is funded, how inequities are approached by research and policies, the countries’ research capacities, and the type of evidence base that MCH policies and programs use. Four tools were designed for these purposes: an online survey for researchers, a semi-structured interview with decision makers, and two content analysis guides: one for policy and programs documents and one for scientific articles. Results: Three modalities of research utilization were observed in the strategies tackling MCH inequities in the six included countries – instrumental, conceptual and symbolic. Instrumental utilization directly relates the formulation and contents of the strategies with research results, and is the least used within the analyzed policies and programs. Even though research is considered as an important input to support decision making and most of the analyzed countries count five or six relevant MCH research initiatives, in most cases, the actual impact of research is not clearly identifiable. Conclusions: While MCH research is increasing in low- and middle-income countries, the impact of its outcomes on policy formulation is low. We did not identify a direct relationship between the nature of the financial support organizations and the kind of evidence utilization within the policy process. There is still a visible gap between researchers and policymakers regarding their different intentions to link evidence and decision making processes.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; Health PEA; L - english / inglês; access to services / acesso a serviços; gender / género; government policy / politica governamental; health - maternal and child / saúde - materno-infantil; health / saúde

O papel da educação para a igualdade de género e empoderamento da mulher em Moçambique: o caso da cidade de Lichinga, 2005-2015 - Lucas, Geraldo Cebola João (Revista Litteris, 2015)
Este artigo tem como objecto “o contributo da educação para a equidade de género e empoderamento da mulher em Moçambique: o caso da cidade de Lichinga, 1997-2015”. O terceiro objectivo do milénio defende que para que possa alcançar o desenvolvimento sustentável nos países em vias de desenvolvimento e mesmo os já industrializados é preciso que a questão de género seja tomada como primordial nas políticas e estratégias de desenvolvimento. E tal pressuposto requer, como se defende nos objectivos, uma equidade de género e seu paralelo empoderamento. Porque acredita-se que a questão de género é transversal. É preocupação nesta pesquisa verificar se as políticas de género em Moçambique estão em consonância com o terceiro objectivo do milénio. Em segundo lugar, verificar o grau do cumprimento do terceiro objectivo do Milénio na cidade de Lichinga. A pesquisa é norteada pela seguinte pergunta de pesquisa: “ em que medida as políticas da educação moçambicana têm contribuído para a equidade e empoderamento do género no quadro do terceiro objectivo do milénio?”.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Lichinga; GP - Niassa; L - portuguese / português; education / educação; empowerment / empoderamento; gender / género; youth / juventude

Challenges and opportunities for implementing evidence-based antenatal care in Mozambique: a qualitative study - Biza, Adriano; Jille-Traas, Ingeborg; Colomar, Mercedes; Belizan, Maria; Requejo Harris, Jennifer; Crahay, Beatrice; Merialdi, Mario; Nguyen, My Huong; Althabe, Fernando; Aleman, Alicia; Bergel, Eduardo; Carbonell, Alicia; et al. (BMC Pregnancy and Childbirth, 2015)
Background: Maternal mortality remains a daunting problem in Mozambique and many other low-resource countries. High quality antenatal care (ANC) services can improve maternal and newborn health outcomes and increase the likelihood that women will seek skilled delivery care. This study explores the factors influencing provider uptake of the recommended package of ANC interventions in Mozambique. Methods: This study used qualitative research methods including key informant interviews with stakeholders from the health sector and a total of five focus group discussions with women with experience with ANC or women from the community. Study participants were selected from three health centers located in Maputo city, Tete, and Cabo Delgado provinces in Mozambique. Staff responsible for the medicines/supply chain at national, provincial and district level were interviewed. A check list was implemented to confirm the availability of the supplies required for ANC. Deductive content analysis was conducted. Results: Three main groups of factors were identified that hinder the implementation of the ANC package in the study setting: a) system or organizational: include chronic supply chain deficiencies, failures in the continuing education system, lack of regular audits and supervision, absence of an efficient patient record system and poor environmental conditions at the health center; b) health care provider factors: such as limited awareness of current clinical guidelines and a resistant attitude to adopting new recommendations; and c) Users: challenges with accessing ANC, poor recognition amongst women about the purpose and importance of the specific interventions provided through ANC, and widespread perception of an unfriendly environment at the health center. Conclusions: The ANC package in Mozambique is not being fully implemented in the three study facilities, and a major barrier is poor functioning of the supply chain system. Recommendations for improving the implementation of antenatal interventions include ensuring clinical protocols based on the ANC model. Increasing the community understanding of the importance of ANC would improve demand for high quality ANC services. The supply chain functioning could be strengthened through the introduction of a kit system with all the necessary supplies for ANC and a simple monitoring system to track the stock levels is recommended.
Keywords: *indexed; *tagged; G - Maputo City / Cidade de Maputo; G - Mozambique / Moçambique; G - central / centro; G - north / norte; G - south / sul; GP - Cabo Delgado; GP - Tete; Health PEA; L - english / inglês; access to services / acesso a serviços; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde

A perspectiva de género no desenho dos programas de protecção social em Moçambique: o caso do programa Acção Social Produtiva - Chiboleca, Gil Tomás; Cremades, Raquel Coello (Faculdade Latino Americana de Ciências Sociais, 2015)
Este trabalho aborda uma das questões centrais no debate sobre a protecção social: género no desenho dos programas de protecção social. Neste contexto, o presente estudo analisa a integração da perspectiva de género no desenho dos programas de protecção social em Moçambique, tomando como estudo de caso – o Programa Acção Social Produtiva. Para a materialização deste trabalho, a nossa proposta de percurso metodológico, em conformidade com os objectivos propostos, o nosso quadro analítico irá guiar-se pelas variáveis centrais: (i) Objectivos gerais e específicos do programa; e (ii) Grupo-alvo (Beneficiários do programa). O estudo constatou que a integração da perspectiva de género nos programas de protecção social é complexa, limitada, e varia de acordo com as características e objectivos de cada programa de protecção social. Ademais, em alguns casos, a consideração de género nos programas é feita através da inclusão das mulheres como principais beneficiárias, ignorando a dimensão do género no seu todo. Na análise do PASP na óptica de género, o trabalho conclui que o programa não incorpora de forma explícita a perspectiva de género, e que a promoção da igualdade de género não constitui um objectivo primário na concepção do PASP. A análise dos grupos-alvo mostra que a consideração de género no PASP é feita através da inclusão da mulher como grupo-alvo prioritário. Isto acontece, como defende o presente estudo, pelo facto do PASP não ter sido desenhado/concebido com o intuito de promover a igualdade de género e empoderamento da mulher, mas para proteger os grupos vulneráveis aliviando a pobreza, e preveni-los contra a indigência e a fome.
Keywords: *tagged; G - Mozambique / Moçambique; L - portuguese / português; gender / género; social protection / proteção social

Child Marriage and Adolescent Pregnancy in Mozambique: Policy Brief - Hodges, Anthony (UNFPA, Meninas e Não Noivas, UNICEF, 2015)
Child marriage is one of Mozambique’s most serious but largely ignored development challenges – requiring far greater attention from policy makers Child marriage rates are still very high despite a long-term decline, especially in marriage before the age of 15. Economic pressures and the incentive of bride price appear to be powerful factors driving parents to marry off their daughters at a young age. The high rates of child marriage cannot be allowed to continue without a vigorous response from the government, civil society and development partners.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde; youth / juventude

Reality checks in Mozambique - Building better understanding of the dynamics of poverty and well-being. Year Four, 2014, sub-report, District of Lago - Tvedten, Inge; Paulo, Margarida; José, Barnabé; Putile, Beatriz (ORGUT Consulting AB, 2014)
The Reality Checks are implemented 2011-2016 and each year field work is carried out in the Municipality of Cuamba, the District of Lago and the District of Majune in the Niassa Province. Each Reality Check focusses on a specific theme. This is the 4th Sub-Report from the District of Lago, focusing on the private sector/entrepreneurship. An Annual Report is produced each year to summarise the findings and conclusions from the three sub-reports.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; GD - Lago; L - english / inglês; gender / género; poverty / pobreza

Measuring Coverage in MNCH: Testing the Validity of Women's Self-Report of Key Maternal and Newborn Health Interventions during the Peripartum Period in Mozambique - Stanton, Cynthia K.; Rawlins, Barbara; Drake, Mary; dos Anjos, Matias; Cantor, David; Chongo, Lidia; Chavane, Leonardo; da Luz Vaz, Maria; Ricca, Jim (PLoS ONE, 2013)
Background: As low-income countries strive to meet targets for Millennium Development Goals 4 and 5, there is growing need to track coverage and quality of high-impact peripartum interventions. At present, nationally representative household surveys conducted in low-income settings primarily measure contact with the health system, shedding little light on content or quality of care. The objective of this study is to validate the ability of women in Mozambique to report on facility-based care they and their newborns received during labor and one hour postpartum. Methods and Findings: The study involved household interviews with women in Mozambique whose births were observed eight to ten months previously as part of a survey of the quality of maternal and newborn care at government health facilities. Of 487 women whose births were observed and who agreed to a follow-up interview, 304 were interviewed (62.4%). The validity of 34 indicators was tested using two measures: area under receiver operator characteristic curve (AUC) and inflation factor (IF); 27 indicators had sufficient numbers for robust analysis, of which four met acceptability criteria for both (AUC .0.6 and 0.75,IF,1.25). Two of these indicators are considered high demand and are recommended for incorporation into international survey programs: presence of a support person during labor/delivery and placement of the newborn skin to skin against the mother. Nine indicators met acceptability criteria for one of the validity measures. All 13 indicators are recommended for use in in-depth maternal/newborn health surveys. Conclusions: Women are able to report on some aspects of peripartum care. Larger studies may be able to validate some indicators that this study could not assess due to the sample size. Future qualitative research may assist in improving question formulation for some indicators. Studies of similar design in other low-income settings are needed to confirm these results.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; Health PEA; L - english / inglês; access to services / acesso a serviços; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde

How active citizens can make a difference to improving service delivery in Mozambique: Phase 1: mapping citizen engagement programmes, initiatives and experiences - Programme, Citizen Engagement (2013)
The Citizen Engagement Program (CEP) supports citizens to monitor the quality of health and education service delivery in 4 of the 11 provinces of Mozambique, as well as to advocate for the improvement of the quality of those services at the district, provincial and national levels. The CEP aims at contributing towards the increased availability of relevant information for citizens to better access and benefit from services delivered by the public sector; improving citizens' capacity to assess service delivery and engage with service providers to improve the quality of health and education services at the primary and secondary levels; and supporting civil society organizations to leverage those findings within decision-making processes at higher levels. The programme will facilitate the dialogue between citizens / communities and service providers to improve the quality of services. The programme supports capacity-building, learning and experimentation, and will develop a robust system of monitoring and evaluation. The CEP will also analyse and build on experiences of service monitoring carried out by other actors and programmes, including other DFID and Irish Aid funded activities.
Accepted: 2017-12-05T13:07:47Z Publisher: (CEP) Citizen Engagement Programme / Cidadania e Participação
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; access to services / acesso a serviços; citizenship & participation / cidadania e participação; decentralization / descentralização; gender / género; health / saúde; ⛔ No DOI found

Reality checks in Mozambique. 2nd Annual Report - Governance - Tvedten, Inge (ORGUT Consulting AB, 2012)
The Reality Checks are implemented between 2011- 2016, with fieldwork being carried out each year in the Districts of Cuamba, Majune and Lago in the Niassa Province. Sub-Team Leaders are Carmeliza Rosário, Minna Tuominen and Inge Tvedten. This is the Annual Report for the 2nd Reality Check, synthesising the main findings from the three sub- reports. The report is written by the Team Leader for the Reality Checks in Mozambique Dr. Inge Tvedten - with support from Carmeliza Rosário, Minna Tuominen and Aslak Orre (Thematic Advisor).
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; gender / género; governance / governação; poverty / pobreza

Avaliação Conjunta do: Apoio à Participação da Sociedade Civil no Diálogo sobre Políticas - ITAD; COWI (ITAD/COWI, 2012)
Estudo de Caso 1. Planificação Distrital e Monitoria do Orçamento Planificação Distrital e Monitoria do Orçamento são processos interligados mas distintos. A Planificação Distrital é um processo de política ao abrigo da LOLE1, segundo a qual a participação das comunidades locais é um princípio básico na governação local e gestão de bens públicos. A planificação distrital é um processo simples, no qual a sociedade civil (SC) local é representada através dos Conselhos Consultivos Locais. O processo de planificação é muitas vezes uma “lista de compras”, sem ligação com a definição de prioridades do orçamento, que é feita ao nível do governo central ou provincial, muitas vezes depois de a planificação ter sido feita a nível distrital. A monitoria sistemática do orçamento é um exercício recente em Moçambique, embora tenha já sido feita sob os auspícios de várias projectos apoiados por Organizações Internacionais da Sociedade Civil (OISCs). Baseia-se na experiência da SC em vários mecanismos de diálogo sobre políticas (por exemplo, Observatórios de Desenvolvimento (ODs)). Estudo de Caso 2. Legislação sobre Violência Doméstica A violência contra a mulher (VCM), em geral, e a violência doméstica contra as mulheres, em particular, constituem um problema global. Em Moçambique, é uma prática generalizada e, infelizmente, largamente aceite, que assenta em sólidos papéis tradicionais de género. Isto é testemunhado por estudos e casos documentados recolhidos por OSCs (WLSA, Le Musica), e por estatísticas dos Gabinetes de Atendimento para mulheres vítimas de violência37. Os casos de violência doméstica contra as mulheres eram, porém, vistos como pertencendo à esfera doméstica (privada) e, assim sendo, não eram considerados uma questão pública; e, até recentemente, não havia nenhum enquadramento jurídico da questão.
Keywords: G - Mozambique / Moçambique; L - portuguese / português; civil society / sociedade civil; gender / género

Promoting Respectful Maternity Care in Mozambique - Reis, Veronica (USAID, 2012)
The objective of this document is to share the results of work undertaken in Mozambique to promote respectful health care, particularly in maternal and neonatal care. With its origins in “humanization of care” efforts in Latin America, this approach centers on the woman and her family and is grounded by principles of ethics and respect for human rights. The approach recognizes a client’s cultural background, and views the client as a person with values and expectations that should be respected during the provision of health care. Respectful maternity care (RMC) emphasizes the fundamental rights of the mother, newborn, and family, and recognizes that childbirth is a deeply personal experience for each woman and her family. In addition, RMC ensures that the client has timely access to health information, privacy, and evidence-based care. Promoting RMC can result in many benefits, including increased service utilization and better health outcomes. It is known that women refuse care from health providers who treat them poorly, even if these providers are capable of preventing or managing obstetric or newborn complications. In countries where a large proportion of births occur outside health facilities, RMC can contribute to increased uptake of maternal and newborn health (MNH) services.
Keywords: G - Mozambique / Moçambique; L - english / inglês; access to services / acesso a serviços; gender / género; health - dignified care / saúde - atendimento humanizado / mau atendimento; health - maternal and child / saúde - materno-infantil; health / saúde

Reality checks in Mozambique: building better understanding of the dynamics of poverty and well-being. Annual Report, Year One - Tvedten, Inge (ORGUT Consulting AB, 2012)
he Reality Checks are implemented 2011-2016 and each year field work is carried out in the Municipality of Cuamba, the District of Lago and the District of Majune in the Niassa Province. This is the Annual Report for Year One of the Reality Checks and aims at summarising the conclusions based on the findings from the field sub-report from each study location.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Cuamba; GD - Lago; GD - Majune; GP - Niassa; L - english / inglês; M - evaluation / avaliação; agriculture / agricultura; gender / género; poverty / pobreza

How do female entrepreneurs perform? Evidence from three developing regions - Bardasi, Elena; Sabarwal, Shwetlena; Terrell, Katherine (Small Business Economics, 2011)
Using the World Bank Enterprise Survey data, we analyze performance gaps between male- and female-owned companies in three regions—Eastern Europe and Central Asia (ECA), Latin America (LA), and Sub-Saharan Africa (SSA). Among our findings are significant gender gaps between male- and female-owned companies in terms of firm size, but much smaller gaps in terms of firm efficiency and growth (except in LA). Part of the reason women run smaller firms is that they tend to concentrate in sectors in which firms are smaller and less efficient (in ECA and SSA). By contrast, we find no evidence of gender discrimination in access to formal finance in any of the three regions, although in ECA women are less likely than men to seek formal finance. Finally, while female entrepreneurs receive smaller loans than their male counterparts, the returns from each dollar they receive is no lower in terms of overall sales revenue.
Number: 4
Keywords: *indexed; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; entrepreneurship / empreendedorismo; gender / género

Gender and the Business Environment for New Firm Creation - Klapper, Leora F.; Parker, Simon C. (The World Bank Research Observer, 2011)
Abstract. The authors summarize the extant literature on the relationship between gender and entrepreneurship. They note significant quantitative gender differ
Number: 2 Publisher: Oxford Academic
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; entrepreneurship / empreendedorismo; gender / género

“All I Eat Is ARVs:” The Paradox of AIDS Treatment Interventions in Central Mozambique - Kalofonos, Ippolytos Andreas (Medical Anthropology Quarterly, 2010)
The number of people on antiretroviral treatment in Mozambique has increased by over 1,500 percent since it first became free and publicly available in 2004. The rising count of “lives saved” seems to portray a success story of high-tech treatment being provided in one of the poorest contexts in the world, as people with AIDS experience dramatic recoveries and live longer. The “scale-up” has had significant social effects, however, as it unfolds in a region with a complicated history and persistent problems related to poverty. Hunger is the principal complaint of people on antiretroviral treatment. The inability of current interventions to adequately address this issue leads to intense competition among people living with HIV/AIDS for the scarce resources available, undermining social solidarity and the potential for further community action around HIV/AIDS issues. Discourses of hunger serve as a critique of these shortcomings, and of the wider political economy underlying the HIV/AIDS epidemic.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - central / centro; Health PEA; L - english / inglês; access to services / acesso a serviços; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde

Gender Dimensions of Investment Climate Reform: A Guide for Policy Makers and Practitioners - Simavi, Sevi; Manuel, Clare; Blackden, Mark C. (The World Bank, 2010)
Promoting women’s economic empowerment is increasingly seen as one of the most important driving forces behind economic growth and the fight against poverty. Women’s economic participation as entrepreneurs, employees, and leaders is recognized as a measure of a country’s dynamism and viability.This main goal of this volume is to provide fresh thinking on how to solve common issues women entrepreneurs and employees face in the investment climate area. It presents actionable, practical, replicable, and scalable tools to promote gender-sensitive investment climate reforms that would equally benefit both women and men. Specifically, the book seeks to enable development practitioners and policy makers who are not gender specialists to diagnose gender issues in an investment climate reform area, design creative and practical solutions and recommendations to address gender constraints, and to oversee the effective monitoring and evaluation of the implementation of those recommendations.This guide highlights the economic rationale for gender inclusion in investment climate reform work and outlines the broader overarching framework within which gender-informed investment climate work can take place. It also provides the monitoring and evaluation framework, with particular emphasis on establishing appropriate baselines to facilitate the measurement of gender-informed changes in the business environment. A step-by-step project management process gives the reader specific guidance on key investment climate areas, namely: (i) business start up and operation, (ii) business taxation, (iii) trade logistics, (iv) special economic zones, (v) alternative dispute resolution, (vi) investment policy and promotion and (vii) secured lending.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; empowerment / empoderamento; entrepreneurship / empreendedorismo; gender / género

Gender and poverty in Mozambique - Tvedten, Inge (CMI, 2010)
Gender equality and women’s empowerment are high on the government and donor agendas in Sub-Saharan Africa, but have largely failed to have an impact. Rather than ‘mainstreaming’ gender, more attention to the variations in the position of women is necessary. In a series of three studies on gender policies and the feminisation of poverty in Mozambique, significant differences were found between the north and the south as well as between rural and urban areas. Such variations are essential to understand in order to design relevant policies and interventions for improving the conditions for women in the country.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; empowerment / empoderamento; gender / género; poverty / pobreza; ⛔ No DOI found

Género e pobreza em Moçambique - Tvedten, Inge (CMI, 2010)
A igualdade de género e o empoderamento das mulheres estão no centro das agendas do governo e dos doadores na África Sub-Sahariana, mas no geral não conseguiram ter impacto. Mais do que a ‘integração’ do género, é necessária mais atenção às variações da posição das mulheres. Numa série de três estudos sobre políticas de género e feminização da pobreza em Moçambique, foram encontradas diferenças significativas entre o norte e o sul, bem como entre as áreas rural e urbana. É essencial que se compreendam estas variações para se desenhar políticas e intervenções relevantes para a melhoria das condições das mulheres no país.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; empowerment / empoderamento; gender / género; poverty / pobreza

Doing Business with the Ladies: Gender, Legal Reform, and Entrepreneurship in the International Finance Corporation - Bedford, Kate (Labour, Capital and Society / Travail, capital et société, 2009)
Since 2007 the World Bank's gender approach has moved away from the Wolfensohn-era emphasis on gender as central to social development concerns, towards a business case model that involves a far greater role for the private sector in efforts to reduce poverty and achieve gender equity. Using a case study of the International Finance Corporation (IFC) and its project, 'Doing Business', to promote the ease of doing business across the world, I ask what this new direction entails for the Bank's gender and development efforts, and examine the new links being forged between gender empowerment and free market reform. The article focuses on three themes in this regard: first, how attention to gender within the 'Doing Business' project helps promote labour market deregulation; second, the contested way in which free markets, legal reform, and gender equality are linked together; and third, the regional reconfigurations of Gender and Development (GAD) evident in the project's report on Women in Africa, wherein women entrepreneurs are celebrated and new networb of GAD specialists are drawn together.
Publisher: Labour, Capital & Society
Keywords: *indexed; *tagged; G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; development partners / parceiros de cooperação; entrepreneurship / empreendedorismo; gender / género; law / direito; ⛔ No DOI found

Programas de saúde materno-infantil em Moçambique: marcos evolutivos e a inserção da enfermagem (Programs of maternal and infant health in Mozambique: gradual landmarks and the insertion of nursing) - Lourenço, Maria Acácia Ernesto; Tyrrell, Maria Antonieta Rubio (Escola Anna Nery, 2009)
See english abstract below. Pesquisa centrada nas políticas públicas do governo moçambicano para o setor da saúde, com foco voltado para programas de assistência à saúde materno-infantil. Tem o propósito de apresentar contextos básicos para a reflexão sobre a filosofia da implantação e implementação dos programas e a inserção da Enfermagem, mostrando seus marcos evolutivos. Constatou-se que, na década 70, o Sistema Nacional de Saúde adotou o Programa de Proteção Materno-Infantil, que na década de 80 ficou concebido como Programa de Saúde Materno-Infantil e, posteriormente, na década 90, ficou inserido no Programa Nacional Integrado de Saúde Materno-Infantil e Planejamento Familiar, Programa Alargado de Vacinação, Saúde Escolar e do Adolescente, incluindo Saúde Sexual e Reprodutiva. A inserção da Enfermagem foi evidenciada na implementação das ações assistenciais. Os marcos evolutivos foram: a introdução dos cursos específicos de Enfermagem em saúde materno-infantil do nível básico ao superior e abrangência dos serviços do Programa Nacional Integrado. ABSTRACT For the interest to know about the public Policies of Mozambican government to the Health sector, this research put much emphasis on the process of implantation and implementation of assistance programs to maternal health looking at reflection about the philosophy of including nursing through ever-changing world or marked changes. Established in the 1970s, the National Health System came up with a maternal health protection program which in the 1980s was drawn into Maternal Health Program. This, in the 1990s was included in the National integrated program of maternal health and family planning, integrating a broad vaccination program, school health and adolescent sexual reproductive health. The inclusion of nursing in the implementation of integrated program became as the evidence through action assistances. The evolutional signs were the introduction of specific courses of Maternal and Infant Health Nursing from basic to superior levels, including the service of National Integrated Program.
Publisher: UFRJ
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; Health PEA; L - portuguese / português; access to services / acesso a serviços; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde; youth / juventude

Gender and Poverty in Northern Mozambique - Tvedten, Inge; Paulo, Margarida; Tuominen, Minna (Chr. Michelsen Institute, 2009)
The main objective of this report is to capture the local configurations of gender relations in Nampula, by focussing on one rural and one urban area in the province. The former is the coastal and rural district of Mossuril, which is considered one of the most deprived districts in the province, both in terms of material poverty and human development (MAE 2005). The urban areas are Muatala and Namutequeliua, which are two of the most populous bairros in the city of Nampula and largely inhabited by migrants from the coast and hence share historical and sociocultural roots with Mossuril.
Keywords: *snowball; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Mossuril; GP - Nampula; Health PEA; L - english / inglês; education / educação; employment / emprego; gender / género; health / saúde; poverty / pobreza

The Environment for Women's Entrepreneurship in the Middle East and North Africa - Chamlou, Nadereh (World Bank, 2008)
This report is about how women entrepreneurs can contribute more to the quality and direction of economic and social development in the Middle East and North Africa (MENA) region. Economic growth in the Middle East has been remarkable since 2004, mainly because of higher oil prices. Rapid job growth has followed, driven mainly by the private sector. Yet the region still faces two important challenges: the first is to create better jobs for an increasingly educated young workforce; the second is to diversify its economies away from the traditional sectors of agriculture, natural resources, construction, and public works and into sectors that can provide more and better jobs for young people— sectors that are more export oriented, labor intensive, and knowledge driven. These goals can be achieved only by more innovative and diverse investors. In this, the private sector must play an even bigger role than in the past. This report is different. Its objective is to provide a better understanding of barriers to investment and doing business that may be common to all investors and those that affect women entrepreneurs disproportionately. The report examines newly available data from more than 4,800 surveyed firms in the formal sector in eight Middle East and North African countries (the Arab Republic of Egypt, Jordan, Lebanon, Morocco, Saudi Arabia, the Syrian Arab Republic, Gaza and the West Bank, and the Republic of Yemen). These surveys detail firm characteristics and the responses of male- and female- owned firms to questions about perceived barriers along 18 categories of the investment climate. The purpose of the report is threefold: • to provide an overview of the characteristics of female- owned firms in the region; • to analyze gender- specific barriers that exist across the region or within countries; and • to identify other factors outside the business environment that might affect women’s entrepreneurship. The report finishes with policy recommendations on how to reduce the identified barriers and create a level playing field for women entrepreneurs. The report acknowledges limitations resulting from the availability and depth of data. It does not attempt to answer every question about women’s entrepreneurship in MENA. Indeed, it may raise more questions than it answers. The hope is to spur greater interest in the topic among researchers and policy makers.
Issue: 44824
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; L - english / inglês; Northern PEA; entrepreneurship / empreendedorismo; gender / género

Sex, Food and Female Power: Discussion of Data Material from Northern Mozambique - Arnfred, Signe (Sexualities, 2007)
Issues of sex and food are often inscribed in male/female relationships. Frequently in a western context sex is perceived as a site of male power and female subordination, while food and cooking are seen as female domains, but still sites of subordination, as elements of women's household chores. In this article, looking at issues of sex and food in a rural matrilineal setting, power aspects of male/female relationships as mediated through sex and food emerge somewhat differently. Sexual proficiency is here a woman's art, mastered by old women and transmitted to the young. Also, in a setting where daily life is largely based on subsistence production, food and cooking become domains of power, again with old women in control. Based on fieldwork in northern Mozambique and with reference to African feminist conceptualizations of male/female power relationships, the article makes a case for rurality and ‘tradition’ not necessarily being adverse to female power in social relationships.
Publisher: SAGE Publications Ltd
Keywords: *indexed; *snowball; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; L - english / inglês; gender / género; youth / juventude

Gender, Entrepreneurship, and Competitiveness in Africa - Bardasi, Elena; Blackden, Mark C.; Guzman, Juan (World Bank, 2007)
This chapter aims to shed light on the nature of men’s and women’s enterprises in Africa, to assess the extent to which the constraints and obstacles faced by women and men entrepreneurs may differ, and to address whether the constraints and obstacles entrepreneurs face affect the productivity and performance of men’s and women’s businesses differently.We begin with a brief overview of gender in the economy, followed by a more detailed analysis of available Enterprise Survey data where key characteristics of businesses can be disaggregated by the sex of the business owner.1 This allows us to look at various characteristics of men’s and women’s businesses, including perceptions of obstacles and constraints, and to assess productivity differences.After briefly placing this analysis in a wider context, the chapter concludes with some recommended actions to address the gender dimensions of entrepreneurship more systematically in policy and programs aimed at supporting private-sector development, along with suggestions for further data collection and analysis.
Keywords: #Reviews & Framing / Revisões e Organização; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; entrepreneurship / empreendedorismo; gender / género

Toward Gender Equality in Mozambique - Van den Bergh-Collier, Edda (Swedish International Development Cooperation Agency (SIDA), 2007)
This is an update of the previous Gender Profi le for Mozambique which was produced in 2000. Sida produces gender profi les for several countries with the purpose of providing a short and concise summary of the gender equality situation in partner countries. The profi e is a desk study reviewing and compiling available statistical material that may be of interest to anyone interested in women’s social, economic and legal position and understanding gender relations in Mozambique. The human development indicators show that signifi cant gender gaps exist in Mozambique. Thus a study of gender relations must repeatedly stress the relative deprivation of women in relation to men. The present profile emphasizes data that illustrates the relative position of men and women rather than attempting to capture and analyze gender relations in the whole country. A detailed discussion of gender relations for each thematic area would require extensive data and sociological/anthropological literature on the construction and dynamics of power relations between men and women in relation to that specifi c aspect of public and private life. For the most part, this kind of data is not available in Mozambique. Thus, the profile gives an overview of the types of issues women face as well as a brief indication of what is being done to address these challenges. Sida has developed generic terms of reference that identify specific issues and topics to be dealt with in individual country profi les. While the updated country profi le for Mozambique addresses all of the issues and topics described in the generic terms of reference, the data is presented in a specific sequence in order to more closely reflect the structure of the PARPA (Poverty Reduction Programme) and PES (Social and Economic Plan) of the Government of Mozambique. The PARPA and PES are central planning instruments for the Government; it is thus considered that this structure highlights potential linkages between Government priorities and Sida’s own development cooperation planning.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; education / educação; gender / género; governance / governação; health / saúde; infrastructure - energy / infrastrutura - energia; infrastructure - roads / infrastructura - estradas; infrastructure / infrastrutura; land governance / gestão de terra; poverty / pobreza; youth / juventude

Gender and economic growthin Kenya: unleashing the power of women - Ellis, Amanda; Cultura, Jozefina; Dione, Nouma; Gillson, Ian; Manuel, Clare; Thongori, Judy (The World Bank, 2007)
This report examines the legal, administrative, and regulatory barriers that are preventing women in Kenya from contributing fully to the Kenyan economy. Building on the 2004 Foreign Investment and Advisory Service (FIAS) report, “Improving the Commercial Legal Framework and Removing Administrative and Regulatory Barriers to Investment,” this study looks at the bureaucratic barriers facing women in Kenya through a gender lens. The report makes specific recommendations to address gender-related barriers in the context of ongoing government and donor initiatives to encourage private sector development as the key driver of poverty reduction and economic growth, in line with Kenya’s Economic Recovery Strategy for Wealth and Employment Creation 2003–2007 (ERS). Addressing these constraints will not only allow women to make a full contribution to the economy but also improve their livelihoods and those of their families and help create a more enabling environment for all businesses in Kenya.
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; L - english / inglês; Northern PEA; gender / género; justice / justiça

Investigação sobre Mulher e Género no Centro de Estudos Africanos - Casimiro, Isabel Maria; Adrare, Ximena (Estudos Moçambicanos, 2005)
Os estudos sobre as relações sociais entre homens e mulheres - das relações de Género - começaram a ganhar corpo a partir de finais da década de 60 os países de língua inglesa - onde foi onstruída a categoria de Género (Gender) - mas depressa se expandiram pelo mundo. Género como categoria análitica, foi e continua a ser o resultado duma interrogação feminista no sentido de esclarecer a subalternidade e subordinação das mulheres no mundo. Trata-se de uma procura que caminhou que continua a caminhar no sentido de interrogações. Não pretendem as suas criadoras feministas o esclarecimento contemplativo por si acerca da discriminação das mulheres. Moveu-as e move-as o desejo de alterar as relações desiguais entre mulheres e homens, no âmbito de construções identitárias que marcam a discriminação entre os seres humanos baseada num poder hierárquico característico do mundo em que vivemos, com o propósito de o transformar.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; gender / género; institutions / instituições; ⛔ No DOI found

Endangering safe motherhood in Mozambique: prenatal care as pregnancy risk - Chapman, Rachel R. (Social Science & Medicine, 2003)
Despite high infant and maternal mortality rates, many Mozambican women with access to prenatal services delay prenatal clinic consultations, limiting opportunity for prevention and treatment of preventable pregnancy complications. Ethnographic research, interviews with health providers and longitudinal pregnancy case studies with 83 women were conducted in Central Mozambique to examine pregnant women's underutilization of clinic-based prenatal services. The study found that pregnancy beliefs and prenatal practices reflect women's attempts to influence reproduction under conditions of vulnerability at multiple levels. Women reported high maternal reproductive morbidity, frequent pregnancy wastage, and immense pressure to bear children throughout their reproductive years. Reproductive vulnerability is intensified by poverty and an intense burden placed on poor, peri-urban women farmers for family subsistence and continuous fertility in a period of economic austerity, land shortages, and increasing social conflict and inequality. In this environment of economic insecurity exacerbated by congested living conditions, women report competing for scarce resources, including male support and income. This vulnerability heightens women's perceptions that they and their unborn infants will be targets of witchcraft or sorcery by jealous neighbors and kin. They respond by hiding pregnancy and delaying prenatal care. Within the context of women's perceived reproductive risks, delayed prenatal care can be seen as a strategy to protect pregnancy from purposeful human and spirit harm. Women mobilized limited resources to acquire prenatal care outside the formal clinic setting. It is concluded that provision of clinical prenatal services is insufficient to reduce reproductive risks for the most socially and economically marginal since it is their vulnerability that prevents women from using available services. Confidential maternity services and social safety nets for greater economic security are recommended.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; Health PEA; L - english / inglês; gender / género; health - maternal and child / saúde - materno-infantil

A gender analysis of the impact of indirect taxes on small and medium enterprises in Vietnam - Akram-Lodhi, A Haroon; van Staveren, Irene (Institute of Social Studies, 2003)
This paper brings together gender analysis, small scale enterprise analysis, and gender budget analysis in a development context. The paper demonstrates that gender matters not only to the ownership of an SME, but also to its most likely principal activity, the stock of the assets that it possesses, the labour that it utilizes, the costs that it faces, the revenues that it generates, and the profits that it earns. In particular, lower earnings for female-owned SMEs can be attributed to the different input cost structures facing female and male-owned SMEs, which in turn are influenced by the indirect tax system. In this context, the paper identifies five gender biases in Vietnam’s VAT system. These biases help explain the higher costs and lower profits of female-owned SMEs in Vietnam. This explanation is different from the more common explanation given for lower performance of female owned enterprises in developing countries, which is the gender segregation of sectors. Although this also plays a role, we argue that gender biases in costs and earnings, partly caused by the tax system, are the more dominant factor.
Keywords: G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; budget / orçamento; gender / género

Discovering normality in health and the reproductive body : proceedings of a workshop held at the Program of African Studies Norhtwestern University - Bledsoe, Caroline; LaRay, Denzer; Glassman, Jonathon; Schoenbrun, David; Ebeling, Mary F. E.; Hansen, Karen Tranberg (Northwestern University's Program of African Studies, 2002)
The papers and discussions included in this collection are the product of a workshop, “Discovering Normality in Health and the Reproductive Body,” held in March, 2001 at Northwestern University's Program of African Studies. The idea for the workshop stemmed from a history of collaborations among Caroline Bledsoe, Jane Guyer, and Kuate Defo Barthélemy on topics of fertility, health, and research methodology. The workshop itself grew out of a commitment to continue that conversation and to expand it to a wider range of people and disciplines. The disciplines represented were wideranging indeed. They included sociocultural anthropology, biological anthropology, history, reproductive biology, history of medicine, public health, and obstetric medicine. The focus of the workshop was Africa, but we also included important comparative cases on South Asia and the Netherlands. In addition we have included those of the discussants' excellent and provocative comments that were available, some of the rapporteurs' notes, and a full list of the participants.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; Health PEA; L - english / inglês; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde; ⛔ No DOI found

Women in Mozambique: Gender Struggle and Gender Politics - Arnfred, Signe (Review of African Political Economy, 1988)
The liberation of women is a fundamental necessity for the revolution, a guarantee of its continuity and a condition for its success (Machel, 1973). In his opening address to the first conference of the Mozambique Women's Organisation (OMM) in 1973, Samora Machel, President of Frelimo, affirmed that women's emancipation was an integral aspect of revolutionary struggle. In 1973 Frelimo was still a liberation front engaged in armed struggle against colonial rule. The northern part of Mozambique was a battle ground and the first OMM conference had to be held in the Frelimo camp at Tunduru in southern Tanzania. In the OMM's present national. secretariat in Maputo, a photograph of the participants of this first conference can be seen. Peasant women and women guerilla's are lined up outside the meeting hut, amongst them Samora Machel in battledress. The non-hierarchical atmosphere depicted in this photograph is in marked contrast to the more formal arrangements on similar later occasions. The participation of women in the war was massive. In 1967, at the request of women themselves, a women's detachment of the guerilla army - Destacamento Feminino - had been formed. Part of its task was to inform and mobilise the peasant population. To support this work, a broader non-military organisation of women was needed. This was the origin of the foundation of the OMM in 1973.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; gender / género